Inorganic fiber-containing multi-element molded unsupported catalyst body for the production of unsaturated aldehydes and unsaturated carboxylic acids, method for producing the same, and use of the same in gas-phase oxidation
Patent Information
- Application Number
- KR1020267030411
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-02-16
- Filing Date
- 2025-02-06
- Publication Date
- 2026-10-21
Smart Images

Figure PCT00001 
Figure PCT00002 
Figure PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a molded unsupported catalyst body for producing unsaturated aldehydes and unsaturated carboxylic acids, wherein the molded unsupported catalyst body comprises at least molybdenum, bismuth, iron, and cobalt elements, and the molded unsupported catalyst body comprises inorganic fibers and has a total pore volume of 0.37 to 0.65 mL / g. Additionally, the present invention relates to a method for manufacturing a molded unsupported catalyst body according to the present invention. Background Technology
[0002] US 2005 / 0065371 describes a molded catalyst body comprising at least molybdenum, bismuth, and iron elements for vapor phase oxidation.
[0003] US 2006 / 0036111 discloses a method for gas-phase oxidation for the production of α,β-unsaturated aldehydes and / or α,β-unsaturated carboxylic acids. In the method, the ignition loss during the calcination process must be within a defined range.
[0004] WO 2015 / 067659 describes a hollow cylindrical molded catalyst body having a defined shape. The molded unsupported catalyst body exhibits high stability and high product-of-value selectivity in the gas-phase oxidation of propene to acrolein and acrylic acid.
[0005] WO 2021 / 239483 discloses a molded unsupported catalyst body having a defined cylindrical structure. The molded unsupported catalyst body enables high packing density and low pressure drop in a fixed catalyst bed.
[0006] EP 0574895, EP 1243331, JP 2011177616, WO 2012 / 036038, WO 2012 / 073584, CN 103861608, WO 2014 / 175113 and JP2019171335 describe the use of fibers in a molded unsupported catalyst body.
[0007] None of the aforementioned literature suggests the importance of simultaneously achieving high catalytic activity and high mechanical stability.
[0008] Accordingly, the object of the present invention was to provide an improved molded unsupported catalyst body for producing unsaturated aldehydes and unsaturated carboxylic acids. The catalyst must exhibit high catalytic activity and mechanical stability.
[0009] Therefore, the present invention provides a molded unsupported catalyst body for producing unsaturated aldehydes and unsaturated carboxylic acids, wherein the molded unsupported catalyst body comprises at least molybdenum, bismuth, iron and cobalt, optionally nickel and potassium elements, wherein the molded unsupported catalyst body comprises inorganic fibers having an average fiber length of 10 μm to 1 mm and an average fiber diameter of 1 μm to 30 μm, and the molded unsupported catalyst body has a total pore volume of 0.37 to 0.65 mL / g, and the total pore volume is determined by the mercury porosity measurement method.
[0010] Preferably, the molded unsupported catalyst body has a total pore volume of 0.39 to 0.60 mL / g, preferably 0.40 to 0.55 mL / g, more preferably 0.41 to 0.50 mL / g.
[0011] Preferably, the inorganic fiber is glass fiber, aluminum oxide fiber, silica fiber, carbon fiber, asbestos, silicon carbide, potassium titanate, or a mixture of the aforementioned fibers. More preferably, the inorganic fiber is glass fiber.
[0012] Preferably, the inorganic fiber has an average fiber length of 25 μm to 750 μm, preferably 50 μm to 500 μm, more preferably 75 μm to 400 μm, and even more preferably 100 μm to 300 μm. Preferably, the inorganic fiber has an average fiber diameter of 3 μm to 18 μm, preferably 5 μm to 15 μm, and more preferably 8 μm to 12 μm.
[0013] Preferably, the composition of the molded unsupported catalyst body corresponds to the following general formula (I):
[0014] Mo 12 Bi a Fe b Co c Ni d X e Y f Z g O n (I)
[0015] In the above formula,
[0016] X = K, Cs and / or Rb,
[0017] Y = Ca, Sr, Ba, Li, Na, Cr, W, Mn, Cu, Zn, Ga, P, B, As, Sn, Sb, Te, Nb, Ta, Pb, Ce and / or La,
[0018] Z = Si, Al, Ti, Zr and / or Mg, and,
[0019] a = 0.2 to 2,
[0020] b = 1 to 4,
[0021] c = 3 to 9,
[0022] d = 0 to 4,
[0023] c + d = 4 to 9.5,
[0024] e = 0.01 to 0.5,
[0025] f = 0 to 10,
[0026] g = 0 to 10, and
[0027] n = a number determined by the valence and abundance of the non-oxygen element in general formula (I).
[0028] Preferably, in general formula (I), X = K, a = 0.4 to 0.8, b = 2.2 to 3.2, c = 4.7 to 7.9, d = 0 to 2.8, c + d = 7.3 to 8.0, e = 0.02 to 0.16, f = 0 and g = 0.
[0029] Preferably, the molded unsupported catalyst body comprises 0.1 to 15 weight%, preferably 0.5 to 13 weight%, more preferably 1.0 to 11 weight%, even more preferably 2 to 10 weight%, particularly preferably 2.5 to 9 weight%, and even more particularly preferably 3 to 8 weight% of inorganic fibers based on the weight of the molded unsupported catalyst body.
[0030] Preferably, the pore volume of the molded unsupported catalyst body in the range of 0.1 to 1 μm is 85 to 99% of the total pore volume, preferably 86 to 98%, more preferably 87 to 97%, even more preferably 88 to 96%, and very preferably 89 to 95%, and the pore volume in the range of 0.1 to 1 μm is determined by the mercury porosity measurement method.
[0031] Preferably, the molded unsupported catalyst body is a compressed molded unsupported catalyst body.
[0032] Preferably, the compressed molded unsupported catalyst body has a density of 1.20 to 1.45 g / mL, preferably 1.22 to 1.43 g / mL, more preferably 1.24 to 1.41 g / mL, and even more preferably 1.26 to 1.39 g / mL, wherein the density of the molded unsupported catalyst body is the ratio of mass to geometric volume.
[0033] Geometric volume is the macroscopic volume of the molded precursor body containing pores. For completeness, it is emphasized that any surface structures, such as substantially circular openings and grooves, notches, or spikes, are not part of the macroscopic volume.
[0034] The present invention also relates to a method for preparing a molded unsupported catalyst body for producing unsaturated aldehydes and unsaturated carboxylic acids, wherein the molded unsupported catalyst body comprises at least molybdenum, bismuth, iron and cobalt, optionally nickel and potassium elements, and wherein
[0035] a) a step of generating an aqueous solution or aqueous suspension from at least one source for each of the elemental components molybdenum, bismuth, iron, and cobalt, and optionally at least one source for each of the elemental components nickel and potassium,
[0036] b) a step of drying and optionally grinding the aqueous solution or aqueous suspension obtained from a) to produce powder P,
[0037] c) A step of mixing powder P obtained from b) with inorganic fibers to produce a powder mixture PM,
[0038] d) a step of compressing the powder mixture PM obtained from c) after optionally adding one or more auxiliary agents, uniform mixing, and optional preliminary compression, to provide a molded precursor body having a cylindrical structure,
[0039] e) A step of forming a molded unsupported catalyst body by applying heat treatment to the molded precursor body obtained from d).
[0040] Includes,
[0041] At this time, the pressure in the compression in d) is selected so that the density of the molded precursor body is 1.65 to 2.20 g / mL, the density of the molded precursor body is the ratio of mass to geometric volume, and the weight loss in the heat treatment in e) is 15 to 50 weight%.
[0042] Geometric volume is the macroscopic volume of the molded precursor body containing pores. For completeness, it is emphasized that any surface structures, such as substantially circular openings and grooves, notches, or spikes, are not part of the macroscopic volume.
[0043] The cylindrical structure is a cylindrical body and preferably has at least one circular opening in the longitudinal direction. In the case of a single opening, the opening is arranged in the center (hollow cylinder). In the case of multiple openings, they are uniformly distributed across the cross-section of the cylindrical structure. A cylindrical structure having three openings is described, for example, by WO 2021 / 239483.
[0044] Heat treatment includes arbitrary thermal pretreatment and actual calcination.
[0045] Preferably, the pressure in the compression in d) is selected such that the density of the molded precursor body is 1.70 to 2.15 g / mL, preferably 1.75 to 2.10 g / mL, more preferably 1.80 to 2.00 g / mL, even more preferably 1.81 to 1.98 g / mL, and even more particularly preferably 1.82 to 1.96 g / mL. The weight loss in the heat treatment in e) is preferably 20 to 45 weight%, preferably 25 to 40 weight%, more preferably 26 to 39 weight%, even more preferably 27 to 38 weight%, even more preferably 28 to 37 weight%, very preferably 29 to 36 weight%, and most preferably 30 to 35 weight%.
[0046] Weight loss in heat treatment can be controlled, for example, by using materials that decompose during heat treatment.
[0047] Preferably, the mixing performed in c) is a dry mixing. Preferably, dry powder P and dry inorganic fiber are mixed together to form a powder mixture PM.
[0048] Preferably, the compression performed in d) is tablet compression.
[0049] Suitable cylindrical structures are a cylindrical body (hollow cylinder) having a central circular opening in the longitudinal direction and a cylindrical body having three uniform notches in the longitudinal direction and three uniformly arranged circular openings in the longitudinal direction. The latter cylindrical structure is described in WO 2021 / 239483.
[0050] The shortest distance between the outer wall of the cylindrical body and the nearest opening is preferably 0.75 to 2.5 mm, preferably 0.8 to 2.0 mm, more preferably 1.0 to 1.8 mm, very preferably 1.2 to 1.7 mm, and most preferably 1.3 to 1.6 mm. In the case of a hollow cylinder, the shortest distance between the outer wall of the cylindrical body and the nearest opening corresponds to the wall thickness of the hollow cylinder.
[0051] Preferably, the composition of the molded unsupported catalyst body obtained by the method according to the present invention corresponds to the following general formula (I):
[0052] Mo 12 Bi a Fe b Co c Ni d X e Y f Z g O n (I)
[0053] In the above formula,
[0054] X = K, Cs and / or Rb,
[0055] Y = Ca, Sr, Ba, Li, Na, Cr, W, Mn, Cu, Zn, Ga, P, B, As, Sn, Sb, Te, Nb, Ta, Pb, Ce and / or La,
[0056] Z = Si, Al, Ti, Zr and / or Mg, and,
[0057] a = 0.2 to 2,
[0058] b = 1 to 4,
[0059] c = 3 to 9,
[0060] d = 0 to 4,
[0061] c + d = 4 to 9.5,
[0062] e = 0.01 to 0.5,
[0063] f = 0 to 10,
[0064] g = 0 to 10, and
[0065] n = a number determined by the valence and abundance of the non-oxygen element in general formula (I).
[0066] Preferably, in general formula (I), X = K, a = 0.4 to 0.8, b = 2.2 to 3.2, c = 4.7 to 7.9, d = 0 to 2.8, c + d = 7.3 to 8.0, e = 0.02 to 0.16, f = 0 and g = 0.
[0067] The present invention also relates to a method for producing unsaturated aldehydes and unsaturated carboxylic acids, wherein alkenes and / or alcohols are induced together with molecular oxygen through a fixed catalyst layer comprising a bed of a molded unsupported catalyst body according to the present invention.
[0068] The present invention also relates to a fixed-bed reactor comprising a bed of a molded unsupported catalyst body according to the present invention.
[0069] The present invention also relates to the use of a molded unsupported catalyst body according to the invention in the gas-phase oxidation of alkenes and / or alcohols.
[0070] The features of the molded unsupported catalyst body according to the invention disclosed herein shall be deemed to be disclosed mutatis mutandis to the method according to the invention for manufacturing the molded unsupported catalyst body, the fixed-bed reactor according to the invention, and the use of the molded unsupported catalyst body, and vice versa. Specific details for implementing the invention
[0071] The present invention is based on the discovery that by using inorganic fibers while simultaneously controlling the total pore volume, a molded precursor body having high catalytic activity and high mechanical stability, particularly suitable for a bed, can be produced.
[0072] The manufacture of such molded unsupported catalyst bodies is described below:
[0073] The molded unsupported catalyst body obtainable according to the present invention is typically formed from a bulk state into a molded body having a geometric shape, and after calcination, is used for catalytic action for each heterogeneous catalytic gaseous partial oxidation (partially the oxidation of propene to acrolein). In principle, the desired shape of the unsupported catalyst is not limited in any way.
[0074] In principle, molded unsupported catalyst bodies can be produced in a simple manner by using a suitable source of their elemental components (particularly components other than oxygen) to produce a very intimate, preferably finely divided, dry mixture of compositions corresponding to each stoichiometry of the molded unsupported catalyst body to be manufactured, molding this mixture into a molded precursor body, which may optionally be combined with a molding aid, and calcining at a temperature of 350 to 650°C. Calcination may be performed under an inert gas or an oxidizing atmosphere, e.g., air (or other mixtures of inert gas and molecular oxygen that may also contain a reducing component in a relatively smaller proportion), or under a reducing atmosphere (e.g., a mixture of inert gas, NH3, CO, and / or H2 that may also contain an oxidizing component in a relatively smaller proportion), or under reduced pressure. The calcination time may be from minutes to days, typically shorter at elevated calcination temperatures.
[0075] A useful source for the elemental component of the molded unsupported catalyst body (i.e., as a starting compound comprising at least one elemental component in a chemically bonded form, which is at least one element present in the molded unsupported catalyst body) comprises a compound that is already an oxide (generally in the solid state of the material under standard conditions (1 atm abs, 0°C) (e.g., metal oxide)) and / or a compound that can be converted into an oxide (generally in the solid state of the material under standard conditions) in the presence of a component that releases at least gaseous oxygen and / or gaseous (e.g., molecular) oxygen by heating (heat treatment at an elevated temperature). In principle, the oxygen source may be a component of the mixture to be calcined, for example, in the form of a peroxide. It is very common for a single starting compound to be a source for two or more elemental components of the molded unsupported catalyst body.
[0076] In addition to oxides, useful starting compounds (sources) of this kind include, in particular, halides, nitrates, formates, acetates, oxalates, citrates, carbonates, amine complexes, ammonium salts and / or hydroxides and also hydrates of said salts.
[0077] Compounds that essentially completely decay and / or decompose to escape in gaseous form (e.g., ammonia, CO2, CO, H2O, nitrogen oxides) during or prior to subsequent calcination, such as NH4OH, (NH4)2CO3, NH4NO3, NH4CHO2, CH3COOH, NH4CH3CO2 and / or ammonium oxalate, may be additionally incorporated into the close dry mixture. Useful materials of this kind that decompose during the calcination process also include organic materials, e.g., stearic acid, malonic acid, ammonium salts of the aforementioned acids, starch (e.g., potato starch, corn starch), crushed nut shells, and finely ground polymers (e.g., polyethylene, polypropylene, etc.).
[0078] If the elemental source from which the very closely and preferably finely divided dry mixture is produced is essentially partially organic (e.g., acetate, formate, oxalate and / or citrate) or contains hydroxide ions, carbonate ions, hydrogen carbonate ions, ammonium ions, halide ions, hydrogen phosphate ions and / or nitrate ions that typically decompose during calcination, gaseous compounds are also typically formed (released) during the outlined heat treatment process.
[0079] Close mixing of the starting compound (source) for the manufacture of the molded unsupported catalyst body can be carried out in a dry or wet form. If carried out in a dry form, the starting compound (source) is appropriately used in the form of a fine powder, and after mixing and compression into a precursor body of geometric shape, it undergoes calcination.
[0080] However, according to the present invention, preferably, close mixing of the (element) source is carried out in a wet form.
[0081] In this case, starting compounds in the form of solutions and / or suspensions are mixed together, and the resulting wet (preferably aqueous) mixture M is dried to obtain a closely spaced dry mixture. The solvent and / or suspension medium used is preferably water or an aqueous solution, and an aqueous mixture M is produced as the wet mixture M.
[0082] A very close dry mixture is obtained in the mixing method described above only when the starting material is a source of elemental components dissolved in a dissolved form and / or in a colloidal form. As previously mentioned, the starting compound may be a source of only one or more elemental components. Correspondingly, the solution or colloidal solution described above may contain only one or more elemental components of the relevant molded unsupported catalyst body to be prepared in a dissolved form. The preferred solvent is, as previously mentioned, water. The drying of the resulting aqueous mixture is preferably carried out by spray drying.
[0083] If this document refers to a solution of a source (starting compound, starting material) in a solvent (particularly, water), the term "dissolution" is intended to mean a molecular or ionic solution. This implies that the largest geometric unit of the dissolved starting material (source) present in the solution necessarily has "molecular" dimensions, and that the solution appears "visually empty."
[0084] In contrast, colloidal solutions constitute a link between a true solution (a molecular and / or ionic solution) and a suspension. In these colloidally dispersed systems, there are smaller accumulations of molecules or atoms, but these are not apparent to the naked eye or under a microscope. Colloidal solutions have a completely transparent (although often colored) visual appearance because the particles present therein have only a diameter of 1 to 250 nm (preferably up to 150 nm and more preferably up to 100 nm).
[0085] Particles dissolved in a colloidal state are so small that they cannot be removed by conventional filtration methods. However, these particles can be separated from the "solvent" by ultrafiltration using membranes of plant, animal, or synthetic origin (e.g., parchment, pig bladder, or cellophane). In contrast to a "visually empty" true solution (molecules and / or ions), light rays cannot pass through a colloidal solution without deflection. Light rays are scattered and deflected by particles dissolved in the colloidal state. To keep colloidal solutions stable and prevent further particle aggregation, they often contain wetting aids, dispersing aids, and other additives.
[0086] For the molded unsupported catalyst body, elements other than silicon (elemental components) are preferably introduced by a source dissolved in the form of a solution for the preparation of a wet (preferably aqueous) mixture M (more preferably in an aqueous solution), whereas elemental silicon is preferably introduced in the form of a silica sol for the preparation of a wet (preferably aqueous) mixture M.
[0087] Silica sol is an aqueous colloidal solution of virtually spherical polysilica particles. The diameter of the particles is in the colloidal range, ranging from 5 to 75 nm depending on the type. The particles are non-pore-free. They possess a core of hydroxylated SiO2 on their surface. The individual spherical particles are not cross-linked with one another. For stability reasons, in silica sol, some of the hydroxyl groups are often in a neutralized form by alkali metal hydroxides—and / or ammonium hydroxides. This is because, in that case, some of the counterions are not protons but alkali metal ions (e.g., Na₂O₃). + ) and / or NH4 + This means that it is (cationic). The SiO2 content of the silica sol suitable for the preparation of a wet (preferably aqueous) mixture M can be, for example, 30 to 60% by weight of the silica sol. The silica sol typically has fluidity similar to water and does not contain any precipitating components. They can often be stored for several years without precipitation.
[0088] A particularly suitable (Si) source is LUDOX from Grace GmbH & KG, In der Hollerecke 1, D-67545 Worms. ® It is a silica sol. Its particles are individual, uniform spheres of silicon dioxide with no internal surface area or detectable crystallinity. The majority of them are dispersed in an alkaline medium that reacts with hydroxylated surfaces to produce a repulsive negative charge.
[0089] The particle diameter of the suitable silica sol can be very narrow (essentially monodisperse) or very wide (polydisperse).
[0090] A silica sol particularly suitable for the purpose of the present invention (preparation of a wet (preferably aqueous) mixture M) is Grace's LUDOX TM50 silica sol. LUDOX TM50 silica sol has a particle diameter distribution that is very substantially monodisperse (d = 22 nm). Its pH (1 atm abs, 25°C) is 9.0. The alkali metal ion replacing the proton portion of the hydroxyl group is Na₂ + The SiO2 content of LUDOX TM50 is 50% of the weight of this hydrogel. The specific surface area of SiO2 particles existing in a colloidal dissolved form in LUDOX TM50 is 140 m² 2 It is / g. The bulk density of LUDOX TM50 (1 atm abs, 25℃) is 1.40 g / cm³. 3 The titrable alkali metal content of LUDOX TM50 (calculated as Na2O) is 0.21 wt% (based on the weight of the silica sol).
[0091] The dynamic viscosity of LUDOX TM50 is 40 mPas (1 atm abs, 25℃). Cl of LUDOX TM50 - The content (calculated in NaCl) is 0.03 wt% and the SO4 of LUDOX TM50 2- The content (calculated as Na2SO4) is 0.08 wt% (based on the weight of LUDOX TM50 in each case).
[0092] It will be understood that in the solution to be used for the preparation of a wet (especially aqueous) mixture M, at least one element source dissolved in a molecular and / or ionic form and one or more other element sources dissolved in a colloidal form may be present side by side.
[0093] A favorable source of Mo is ammonium heptamolybdate tetrahydrate. This is because it has excellent solubility, particularly in water. According to Ullmann's Encyclopedia of Industrial Chemistry, volume 22, 2003, WILEY-VCH, pages 320 / 321, a solution of ammonium molybdate tetrahydrate in water at 25°C and 1 atm abs has a saturated solubility of 30 wt% (calculated as an anhydrous salt).
[0094] As a result of manufacturing, ammonium molybdate tetrahydrate may be contaminated with small amounts (typically ppm) of water-insoluble isopolymolybdate (as a result of method parameters not accurately observed in its manufacturing). When ammonium heptamolybdate tetrahydrate contaminated in this way is dissolved in water, it results in an aqueous solution with a certain turbidity due to small amounts of finely fragmented isopolymolybdate existing in an undissolved form. According to the applicant's in-house research, even isopolymolybdate-contaminated ammonium molybdate tetrahydrate having a turbidity of 20 NTU, or 50 NTU, or 70 NTU, or 100 NTU, or 150 NTU, or 200 NTU, or 250 NTU, or 300 NTU in water (determined as described in WO 2016 / 147324) was found to be suitable for the manufacture of the molded unsupported catalyst body of the invention without any discernible impairment to its performance when used as a catalyst for heterogeneous catalytic partial gas phase oxidation with acrolein of propene as the main product and acrolein as a byproduct.
[0095] Additional suitable Mo sources are, for example, ammonium orthomolybdate ((NH4)2MoO4), ammonium dimolybdate ((NH4)2Mo2O7), and ammonium tetramolybdate dihydrate ((NH4)2Mo4O). 13x 2 H2O) and ammonium decamolibdate dihydrate ((NH4)4Mo 10 O 32 x 2 H2O). However, in principle, molybdenum trioxide can also be used.
[0096] In the context of manufacturing molded unsupported catalyst bodies, a preferred source of alkali metals is their hydroxides. However, in principle, nitrates of these elements and hydrates of these nitrates are also useful as such sources. This means that while the preferred (K) source is KOH, KNO3 or its hydrates can also be used as K sources in principle.
[0097] The Bi source used is Bi Bi 3+ It is preferable that the salt be of bismuth having the form of. Examples of useful salts of this kind include bismuth(III) oxide, bismuth(III) oxide nitrate (bismuth subnitrate), bismuth(III) halides (e.g., fluoride, chloride, bromide, iodide), and in particular bismuth(III) nitrate pentahydrate. The Bi source used also includes Bi where Bi is Bi 3+ You will understand that it may be a solution of the element Bi in aqueous nitric acid in the form of Bi. 3+ When an aqueous solution of nitrate or its hydrate is used as a source (preferably according to the invention) (such a solution can also be prepared by dissolving elemental Bi in aqueous nitric acid), it is advantageous according to the invention when its pH (1 atm abs, 25°C) is low, as Bi in the aqueous solution 3+ This is because it prevents the unwanted formation of precipitates. The pH is preferably ≤ 1, more preferably ≤ 0.5. Generally, however, the pH is ≥ -2, usually ≥ 0. Appropriately, this aqueous solution is a nitric acid solution. This means that its low pH is caused by an excess of nitric acid (in this case, NO3 present in the aqueous solution).- molar amount of (n NO3- ) and Bi3 present in aqueous solution + molar amount of (n Bi3+ The molar ratio of ) (n NO3- ) / (n Bi3+ ) is > 3).
[0098] The desirable (Fe) source is Fe 3+ It is a salt of, among which various iron(III) nitrate hydrates are particularly preferred (see, for example, DE 10 2007 003076 A1). According to the invention, it is particularly preferred to use iron(III) nitrate hydrate as a source of Fe for the aforementioned purposes. Fe as a source of Fe 2+ Of course, it is also possible to use salt.
[0099] Advantageously, for the manufacture of a molded unsupported catalyst body, based on the total molar amount of Fe present therein, at least 50 mol%, more preferably at least 75 mol%, and preferably at least 95 mol% or 100 mol% of Fe is Fe 3+ It is introduced in the form of an Fe source having the form of. For this purpose, Fe 3+ and Fe 3+ It is also possible to use an Fe source that has all of the above.
[0100] A particularly suitable Co source is Co Co 2+ and / or Co 3+ It is a salt having the form of. Examples of these include cobalt(II) nitrate hexahydrate, Co3O4, CoO, cobalt(II) formate, and cobalt(III) nitrate. For the aforementioned purpose, the first of these sources is particularly preferred. The Co source used also includes Co where Co is Co 2+ You will understand that it may be a solution of element Co in aqueous nitric acid in the form of
[0101] In the case of the elemental component (Ni), Ni 2+It is preferable to use salts. These include, in particular, nickel(II) carbonate, nickel(II) sulfate, nickel(II) oxide, nickel(II) acetate, nickel(II) formate, nickel(II) hydroxide, nickel(II) oxalate, and nickel(II) nitrate, and their respective hydrates. It is particularly preferable to use a hydrate of nickel(II) nitrate (e.g., its hexahydrate) as a source of Ni. The Ni source used also contains nickel Ni 2+ You will understand that it may be a solution of elemental Ni in aqueous nitric acid in the form of. Such a solution also typically contains ammonium nitrate in a specific proportion.
[0102] For example, the solubility of salts of Fe, Co, and / or Ni in an aqueous medium can be improved by adding ammonia (or an aqueous solution thereof) and / or nitric acid (especially as an aqueous solution thereof) to each solution if necessary.
[0103] In principle, the preparation of a wet (e.g., aqueous) mixture M can be carried out under various gaseous atmospheres (e.g., air, argon, nitrogen, steam, and / or carbon dioxide). According to the invention, preferably, the preparation of the wet (e.g., aqueous) mixture M is carried out under air (advantageous, the aqueous mixture M is saturated with air). This is because the cobalt and iron sources used are Co 2+ Salts and Fe 2+ This is especially true in the case of salts. This is especially true when such salts are nitrates and / or their hydrates.
[0104] As previously mentioned, the wet mixture M is an aqueous mixture M that is preferably, in accordance with the present invention, prepared in the following manner, which is particularly advantageous.
[0105] An aqueous solution A is prepared using at least one source of element Fe, at least one source of element Bi, at least one source of element Co, and optionally at least one source of element Ni, such that the pH is ≤ 3, preferably ≤ 2, more preferably ≤ 1, and most preferably ≤ 0 (the pH value of the aqueous solution is (unless otherwise explicitly stated herein) generally 1 atm abs and the temperature at which each aqueous solution is prepared using a glass electrode in the form of a combination electrode; calibration of the combination electrode required for this purpose is performed under the same conditions using an aqueous buffer solution having a known pH under these conditions and close to the measurement to be obtained; the Mettler Toledo Inpro 4260 / 425 / Pt 100 pH electrode is particularly suitable for determining such pH value, which is a combination electrode having an integrated Pt 100 temperature sensor for automatic temperature compensation). Generally, the pH of the aqueous solution A is -2 or higher and, particularly advantageously, in the range of -1 to 0. Preferably, aqueous solution A is an aqueous solution of the nitrate or nitrate hydrate of the aforementioned element. More preferably, aqueous solution A is an aqueous solution of such nitrate or nitrate hydrate in aqueous nitric acid. Particularly for the preparation of such a solution, a suitable source of the element is also a solution of the relevant element in aqueous nitric acid.
[0106] Aqueous solution B is prepared using at least one source of elemental Mo and optionally at least one source of an alkali metal. The pH of aqueous solution B (at 1 atm abs and at the temperature at which solution (B) is prepared) is advantageously < 7. More preferably, the pH of aqueous solution B is ≤ 6.5 and very particularly advantageously ≤ 6. In general, the pH of aqueous solution B will be ≥ 3. Solution (B) advantageous for use according to the invention has a pH of 4 to 6. According to the invention, preferably, for the preparation of aqueous solution B, the source of the alkali metal used is its elemental hydroxide (e.g., KOH). A preferred source of Mo for the preparation of aqueous solution B is ammonium heptamolybdate tetrahydrate ((NH4)6Mo7O 24 x 4 H2O), which is completely soluble in water up to saturation solubility (calculated in anhydrous form, 30 wt%) at 25°C (1 atm abs).
[0107] Appropriately according to the present invention, the total content of metal components (Bi, Fe, Co, Ni), etc. in aqueous solution A is 5 to 20 weight%, advantageously 10 to 15 weight%, based on the total amount of aqueous solution A.
[0108] Appropriately according to the present invention, the total content of Mo in aqueous solution B is 2 to 25 weight%, advantageously 3 to 20 weight%, and particularly advantageously 5 to 15 weight% based on the total amount of aqueous solution B.
[0109] Next, aqueous solution A and aqueous solution B are mixed together appropriately. At this stage, it is advantageous to continuously add aqueous solution A while stirring aqueous solution B. It is advantageous to perform this while vigorously stirring the aqueous solution B initially added.
[0110] Appropriately according to the present invention, the total content of metal components (Bi, Fe, Co, Ni, Mo), etc. in the aqueous mixture formed from aqueous solution A and aqueous solution B is 3 to 20 weight%, advantageously 5 to 15 weight%, based on the total amount of the aqueous mixture.
[0111] The temperature of the aqueous solution B initially added, the temperature when adding the aqueous solution A while stirring (stirring-in), and the temperature of the aqueous solution A itself are advantageously ≤ 80°C and ≥ 0°C (preferably during the entire mixing method). Preferably, the temperatures are ≤ 75°C and ≥ 30°C, and more preferably, they are ≤ 70°C and ≥ 50°C or ≤ 65°C and ≥ 55°C, respectively.
[0112] Advantageously, aqueous solution A, aqueous solution B, and the aqueous mixture formed when aqueous solution A is added to aqueous solution B while stirring have the same temperature. Ideally, this is 60°C. Preferably, the temperature of aqueous solution A, aqueous solution B, and the aqueous mixture formed therefrom is constant during the process of the described stirring addition method. For this purpose, temperature control can be achieved, for example, by using a water bath. The operating pressure when adding aqueous solution A while stirring aqueous solution B is suitably 1 atm abs (1.01 bar).
[0113] Preferably, aqueous solution A is added while stirring the initially added aqueous solution B within a period ranging from 5 to 60 minutes, more preferably within a period of 10 to 30 minutes, and most preferably within a period of 15 to 25 minutes. The resulting aqueous mixture is then appropriately stirred for an additional 5 to 60 minutes, preferably 10 to 30 minutes, and particularly advantageously 15 to 25 minutes, while preferably maintaining the stirring addition temperature.
[0114] The pH of the aqueous mixture of solution A and solution B is advantageously ≤ 3, better ≤ 2. In general, it is at a value ≥ 0.
[0115] If the molded unsupported catalyst body contains an elemental component (Si), according to the present invention, it is preferable to add an aqueous silica sol as a source thereof to an aqueous mixture of aqueous solution A and aqueous solution B while stirring, in which case water may be added to the aqueous mixture before stirring. In a suitable manner, both the aqueous silica sol and water may be added at once. It is advantageous for the temperature of the water and the temperature of the aqueous silica sol to be equal to the temperature of the aqueous mixture of aqueous solution A and aqueous solution B. Finally, stirring is appropriately continued for up to 30 minutes. During additional stirring, the aforementioned temperature is advantageously maintained. The SiO2 content of the added aqueous silica sol may be 15 to 60 wt%, or 20 to 60 wt%, or 30 to 60 wt%, preferably 40 to 60 wt%, and more preferably 45 to 55 wt% (based on the total weight thereof in each case).
[0116] Instead of initially adding aqueous solution B to a constant-temperature stirred vessel and supplying aqueous solution A while stirring, it is also possible to continuously supply both aqueous solution B and aqueous solution A to the stirred vessel (e.g., via a "3-way T-mixer"). In principle, aqueous solution B may also be continuously stirred and added to the initially added aqueous solution A. However, this procedure is relatively undesirable.
[0117] Generally, the aqueous mixture M obtainable as described is an aqueous suspension (preferably, the ratio (V) described as advantageous is also present in the aqueous mixture M (present NH3+ NH4 +The total molar amount of Mo relative to the molar amount of Mo present); additionally, the pH of the aqueous mixture M obtainable as described is also advantageously ≤ 3, generally 0 to 2). The aqueous mixture M obtainable as described advantageously contains 60 mol% or less of the total molar amount of Co and / or Ni present therein in a form dissolved in an aqueous medium (at the temperature and operating pressure at which the aqueous mixture M is prepared). Preferably, the above-described ratio (AT) of the molar amount of Co and / or Ni total present in the aqueous mixture M dissolved in the aqueous medium is at a value of ≤ 90 mol%, and more preferably at a value of ≤ 90 mol%, or ≤ 70 mol%, or ≤ 60 mol%. Appropriately according to the invention, the total content of Bi, Fe, Mo, etc. in the aqueous mixture M to be dried (preferably spray-dried) is 3 to 20 weight%, advantageously 5 to 15 weight% based on the amount of the aqueous mixture M. Generally, AT is ≥ 3 mol%, or ≤ 50 mol%.
[0118] Preferably according to the present invention, an aqueous mixture M is converted into a finely divided, closely dry mixture by spray-drying the aqueous mixture M (it is preferable that the aqueous mixture M be dried as soon as possible after its preparation). This means that the aqueous mixture M is first divided (sprayed) into fine droplets in a spray dryer and then dried in a spray dryer. Spray drying is preferably performed in a high-temperature air stream. In principle, for the aforementioned spray drying, it is possible to alternatively use other high-temperature gases (e.g., nitrogen or nitrogen-diluted air and other inert gases).
[0119] Spray drying can be performed with a concurrent or countercurrent flow of droplets against a high-temperature gas. A typical gas inlet temperature is in the range of 250 to 450°C, preferably 270 to 370°C. A typical gas outlet temperature is in the range of 90 to 160°C. Preferably, spray drying occurs with a concurrent flow of droplets against a high-temperature gas.
[0120] The average particle diameter of the generated spray powder is typically 10 to 100 μm, preferably 15 to 60 μm, and more preferably 25 to 50 μm (the diameter is determined according to ISO 13320-1 by light scattering for air-dispersed spray powder (dispersed air pressure 1.0 bar). Generally, references to standards herein relate to the version of the standard that was effective on the priority date of this patent application in each case and has the smallest time difference from the priority date of this patent application.
[0121] The tap bulk density of the spray powder (25°C, 1 atm abs) is typically 500 to 1300 g / L and preferably 700 to 1100 g / L.
[0122] The loss on ignition of the spray powder (calcined at 600°C (powder temperature) under excess stagnant air for 3 hours) is typically 20 to 40 weight% of its initial weight, preferably 25 to 35 weight%.
[0123] Until further processing, the spray powder may preferably be stored in an airtight container (e.g., a drum made of plastic). The storage temperature must not exceed 70°C and is preferably ≤ 50°C. Generally, the storage temperature is 10°C or higher. Since the spray powder is generally hygroscopic, prolonged contact with humid air should be avoided. Contact with humid air can impair the handling characteristics of the spray powder (e.g., its fluidity) and ultimately reduce the catalytic activity of the molded unsupported catalyst body made from it.
[0124] It will be understood that the aqueous mixture M can also be dried by other drying methods, for example, conventional evaporation (preferably under reduced pressure; the drying temperature will generally not exceed 150°C). In principle, the drying of the aqueous mixture M can also be performed by freeze-drying or Spin-Flash® drying.
[0125] The spray powder may be coarsely ground first, for example, by subsequent pre-compression. "Pre-compression" means the pre-compression of the powder prior to subsequent compression to produce a molded precursor body. If the pre-compression is performed in a dry form, the finely divided graphite and dry inorganic fibers and / or other molding aids (e.g., lubricants, reinforcing agents and / or pore-forming agents) specified herein may be mixed, for example, into the spray powder prior to the pre-compression. Mixing takes place in a mixer, for example, a drum hoop mixer, a tumble mixer, a ribbon mixer, a paddle mixer, and a high-strength mixer, preferably in a mixer having scissors action, for example, a mixer equipped with a chopper.
[0126] For example, pre-compression can be performed using a calender with two counter-rotating steel rolls. Subsequently, the pre-compressed material can be specifically ground to a particle size suitable for further use being considered. The simplest way to do this is, for example, to force the pre-compressed material through a sieve having a specified mesh size.
[0127] In principle, pre-compression can alternatively be performed in a wet form. For example, spray powder can be kneaded with the addition of water. After kneading, the kneaded composition can be ground again to a predetermined fineness for subsequent use (see, for example, DE 100 49 873 A1) and dried.
[0128] A finely divided precursor composition (a finely divided, close dry mixture of sources of elemental components) is used to form a molded precursor body of a regular or irregular shape by compression (also called tableting), and said molded precursor body is then used to produce a molded unsupported catalyst body by heat treatment.
[0129] Additional finely divided molding aids that may be added to the finely divided precursor composition before and / or during molding are, for example, re-lubricants, for example, graphite, carbon black, polyethylene glycol, polyacrylic acid, stearic acid, starch, mineral oil, vegetable oil, water, boron trifluoride and / or boron nitride. Other useful molding aids are pore-forming agents such as ammonium nitrate, ammonium carbonate, water and / or malonic acid. The pore-forming agent decomposes or evaporates during heat treatment to form pores. The concomitant use of lubricants in the context of corresponding forming operations is described, for example, in documents DE 10 2007 004961 A1, WO 2008 / 087116, WO 2005 / 030393, US 2005 / 0131253, WO 2007 / 017431, DE 10 2007 005606 A1 and DE 10 2008 040093 A1.
[0130] It is preferable to use only finely divided graphite as a lubricant. The finely divided graphite to be used herein is that which is particularly recommended in WO 2005 / 030393, US 2005 / 0131253, WO 2008 / 087116, and DE 10 2007 005606 A1. This is especially true for the graphite used in the examples and comparative examples of these documents. Highly preferred graphite is Asbury Graphite Mills, Inc., Asbury 3160 and Asbury 4012, New Jersey 08802, USA, and Timrex, Timcal Ltd., 6743 Bodio, Switzerland. ® It is T44.
[0131] Based on the weight of the finely divided precursor composition to be molded, it may contain, for example, up to 15 weight percent of a finely divided lubricant (e.g., graphite) based on its total weight. However, usually, the lubricant content in the finely divided precursor composition to be molded (finely divided close dry mixture) is ≤ 9 weight percent, and in many cases ≤ 5 weight percent, often ≤ 4 weight percent; this is especially true when the finely divided lubricant is graphite. Generally, the aforementioned amount of addition is ≥ 0.5 weight percent, and usually ≥ 2.5 weight percent.
[0132] Generally, a finely divided precursor composition (a finely divided, closely spaced dry mixture) optionally containing a molding aid is compressed into the desired shape of a molded precursor body by the application of an external force (pressure) to the precursor composition. The molding device or molding method to be used herein is not subject to any limitations.
[0133] For example, compression molding may be performed by tableting. The finely divided precursor composition (finely divided close dry mixture) used herein is preferably dry upon contact. However, up to 10% of its total weight, it may contain an added material that is liquid under standard conditions (e.g., 25°C, 1 atm abs (1.01 bar)). The finely divided precursor composition (finely divided close dry mixture) may also contain a solid solvate (e.g., a hydrate) containing such liquid material in a chemically and / or physically bonded form. It will be understood that the finely divided precursor composition may not contain such material at all.
[0134] A preferred method of forming by compression of a finely divided precursor composition (a finely divided, closely spaced dry mixture) is tablet compression. The principle of tablet compression is described, for example, in “The Tablet”, Handbook of Development, Production and Quality Assurance, WA Ritschel and A. Bauer-Brandl, 2nd edition, Edition Verlag Aulendorf, 2002, and is applicable in a manner that fully corresponds to the tablet compression method of the present invention.
[0135] Tablet compression is a pressure aggregation method. A free-flowing feed mixture is introduced into a press die having a die between two punches, compressed by uniaxial compression, and formed into a solid compressed body. Tablet compression can be divided into four stages: quantitative feeding, compression (elastic deformation), plastic deformation, and discharge. Tablet compression is performed, for example, in a rotary press or an eccentric press.
[0136] The outer surface of the compressed catalyst carrier consists of a circumferential surface corresponding to the inner wall of the die cavity, and a first end face and a second side face corresponding to the working head of the punch. The compressed catalyst carrier may have a flat or curved end, which means that at least one of the first side face and the second side face is curved. The curved side face may be obtained, for example, by using a concave lower and / or upper punch. If desired, the upper punch and / or lower punch may include protruding pins to form an internal passage. It is also possible to provide a number of pins to the press punch; for example, a punch having four pins may be manufactured to produce a molded body having four holes (passages). Typical configuration features of such a press die can be found, for example, in US 8,865,614.
[0137] A press die typically consists of a die, an upper punch, a lower punch, and a pin (if the formed body has a passage). Suitable materials for the press die are tool steel, tungsten carbide (WC)-based cemented carbide, and ceramic materials. Tool materials having a hardness of 55 or greater on the Rockwell C scale are preferred. Examples of tool steel materials include DIN tool steels 1.2210, 1.2343, 1.2436, 1.2379, 1.2601, 1.2080, 1.25550, and high-speed steels, Uddeholm, D-40549 Düsseldorf Vanadis 4 Extra, and Uddeholm, D-40549 Düsseldorf Vanadis 8. Suitable WC-based materials are described in US 8,865,614. Examples of such WC-based materials include G10-Ni from Hartmetall® Gesellschaft in D-70497 Stuttgart and htc-KR17® from Hightech-Ceram®. An example of a ceramic material is yttrium-stabilized zirconia (YSZ).
[0138] WC-based hard carbide and ceramic materials are particularly suitable for use as tool materials, in which case a lined die made of WC-based hard carbide or ceramic is inserted into a steel housing made of tool steel, for example 1.2379.
[0139] Press molds typically have a surface coating to improve surface hardness, corrosion resistance, wear resistance, friction, and non-stick properties. Examples of surface coating types include diamond-like carbon (DLC), boron nitride, titanium nitride, chromium nitride, chrome plasma coating, and hard chrome plating. The thickness of the layer is 1 to 10 μm, preferably 1 to 5 μm.
[0140] The surface of the press mold in contact with the feed mixture and the produced tablets preferably has low surface roughness. The arithmetic mean roughness Ra of the press mold surface according to DIN 4768 should preferably be 0.01 to 0.5 μm, more preferably 0.02 to 0.3 μm, much more preferably 0.02 to 0.2 μm, and very preferably 0.02 to 0.1 μm.
[0141] The length of the tip, particularly the lower punch, is preferably 2 to 7 mm, particularly preferably 2 to 6 mm, and very preferably 2.5 to 5 mm. An excessive tip length can lead to high friction, especially when adhesion of the molded precursor body occurs. The upper and lower edges of the tip, specifically the lower jaw, are preferably sharp rather than rounded. Sharp edges alleviate powder clogging at the edges of the punch-die interface and the pinhole interface (in the case of a tablet die with a passage). Powder clogging leads to both adhesion and escape of the powder.
[0142] The length of the tip, particularly the upper punch, is preferably greater than 2 mm and typically ranges from 2 to 10 mm. In contrast to the lower punch, the upper punch is inserted only a few millimeters into the die during the tableting cycle, so a high tip length does not cause friction problems.
[0143] If the tablet shape has a passage, the lower punch and the upper punch have holes for receiving pins. The upper punch must have at least one ventilation hole to allow air to escape from the die cavity through the upper punch hole to the outside of the upper punch hole during compression. Such an upper punch having a ventilation hole is specified in US 2010 / 0010238 (see FIGS. 4a, 4b, 4c and 4d).
[0144] The distance between the die bore and the lower outer surface of the punch is preferably 3 to 50 μm, more preferably 5 to 35 μm, and very preferably 6 to 26 μm. Similarly, the distance between the die bore and the upper outer surface of the punch is preferably 3 to 50 μm, more preferably 5 to 35 μm, and very preferably 6 to 26 μm. The distance is ensured by the selection of a suitable combination of dimensional tolerances for the die and the lower punch. Dimensional tolerances are typically expressed by the ISO wave tolerance scheme defined in ISO 286-2. Examples of combinations of dimensional tolerances for the die bore and the outer surface of the punch expressed by ISO tolerance codes are H6 / f7, H6 / g6, H6 / g7, H7 / g6, H7 / f7, F8 / h6, G7 / h6, and F7 / h6 (lower outer surface of the die bore / punch).
[0145] When the tablet shape has a passage, the press die includes a pin. The distance between the pin bore of the lower punch and the pin is preferably 3 to 50 μm, more preferably 5 to 35 μm, and very preferably 6 to 26 μm. Similar to the distance between the die bore and the outside of the punch, this distance is ensured through the selection of a suitable combination of dimensional tolerances of the die and the lower punch.
[0146] The die bore preferably has a slight taper starting from a defined depth in the direction of the upper end of the die. The tapering portion of the die bore features a gradual increase in bore size in the direction of the upper end of the die, which creates additional distance between the die bore wall and the inclined outer side of the lower punch. This additional space facilitates the escape of air present in the mixed feed during compression in the die, thereby mitigating powder blowing and resulting unstable tableting caused by poor air escape. An additional advantage of the conical die is that ejection after compression is facilitated. Compression forming into a tablet at the point where the die bore tapers results in a tablet having a slightly tapered outer side due to forming with the conical die bore. During the ejection stage, where the lower punch pushes the tablet upward in the die, the tablet is easily ejected from the die wall because the slight rise of the tablet separates it from the die wall due to the tapered structure. If the die bore does not have a taper, the tablet is not separated from the die wall, so the entire ejection method (i.e., pushing the tablet up above the top of the die from the depth at which compression occurs) is difficult due to friction between the outer surface of the tablet and the die wall, and between the straight outer surface of the tip and the die wall. Friction leads to an adversely high ejection force.
[0147] The depth of the die taper (i.e., the depth from the top side of the die) should be selected so that the tablet formed before ejection is mainly in the conical zone. To achieve this, the depth of the die taper can be determined by adding the height of the in-die tablet before elastic recovery (i.e., the minimum distance between the upper and lower punches) and the insertion depth of the upper punch. For example, a taper depth of 12 to 15 mm can be used for a 12 mm in-die tablet height with an insertion depth of 2 mm of the upper punch.
[0148] The angle of the die taper is typically 0.1 to 0.6°, and the increase in size of the die bore on the upper side is preferably 0.03 to 0.2 mm, particularly preferably 0.05 to 0.14 mm. The increase in size can be mathematically derived from the angle of the taper and the taper depth.
[0149] If the tablet shape has a passage, the press die includes a pin. Since the pin is fixed to the revolver, it is present in the die cavity where the tablet is formed to leave a passage for the tablet. Similar to the die, the pin does not move vertically during the tableting cycle, in contrast to the upper and lower punches. The vertical plane of the upper end of the pin is equal to or slightly below the height of the upper end face of the die. Particularly for tablets having curved sides with a concave surface on the lower punch face, the vertical plane of the upper end of the pin must be slightly below the level of the upper front side of the die so that the pin does not protrude from the lower punch face.
[0150] When the tablet shape has a passage, adhesion frequently occurs on the surface of the pins, leading to defects such as high ejection force due to high friction at the pin-tablet interface. This problem is particularly pronounced in the case of multi-die systems with multiple pins. Typically, pins have a higher tendency for adhesion than the die walls and, specifically, the tips of the lower jaws.
[0151] When the tablet shape has a passage, the pin preferably has a slight taper in the upper region for a defined length. The tapered portion of the pin shows a gradual decrease in the pin diameter toward the upper end of the pin. The main advantage of a conical pin is that ejection after compression is facilitated. Compression forming into a tablet at the position where the pin has a taper leads to a tablet passage having a slightly tapered inner side as a result of forming with the tapered pin. The diameter of the tablet passage decreases slightly upward along the axial axis from the bottom. In the ejection stage, where the lower punch pushes the tablet upward from the die and the pin and die do not move horizontally, the tablet is easily ejected from the pin because the slight rise of the tablet causes it to separate from the pin due to the tapered structure. If the pin does not have a taper, separation of the tablet from the pin does not occur, so the entire ejection method (i.e., lifting the tablet from the depth at which compression is performed against the upper end face of the die) is difficult due to friction at the tablet-pin interface, which leads to a high ejection force. Conical pins are particularly advantageous when the tablet has multiple channels.
[0152] The length of the pin's taper should be selected so that the tablet formed before ejection is mainly in the conical zone. To achieve this, the length of the pin's taper can be determined by adding the height of the tablet in the die before elastic recovery (i.e., the minimum distance between the upper and lower punches) and the insertion depth of the upper punch. For example, a tapering length of 12 to 15 mm can be used for a tablet height of 12 mm in the die with an insertion depth of 2 mm of the upper punch.
[0153] The angle of the die taper is typically 0.1 to 0.6°, and the reduction in pin diameter on the upper side is preferably 0.05 to 0.3 mm, particularly preferably 0.1 to 0.2 mm. The reduction can be mathematically derived from the angle of the taper and the taper length.
[0154] The industrial mass production of tablets is preferably carried out in a rotary tablet press. Conventional commercial rotary presses may be used for this invention. Examples of rotary tablet presses are Korsch XT-600 HD, Korsch XT-600, Korsch TPR 700, Korsch TRP 1200, Korsch XL 400 MFP, Kilian RX, and Kilian Synthesis.
[0155] A rotary press typically has two compression rolls to perform two-stage compression, including pre-compression and main compression. The main compression pressure is in the range of 5 to 500 MPa, preferably 8 to 400 MPa, more preferably 10 to 300 MPa. The pre-compression pressure is typically in the range of 5% to 50%, preferably 7% to 40%, more preferably 10% to 35% of the applied main compression pressure.
[0156] A press die is selected according to the desired geometric dimensions of the compressed body. The size and shape of the compressed body and thus the catalyst are selected to enable suitable packing of the catalyst body obtained from the compressed body within the reactor tube. The catalyst obtained from the compressed body suitable for the catalyst of the invention is preferably used in a reactor tube having a length of 6 to 14 m and an inner diameter of 20 mm to 50 mm. Generally, the carrier consists of individual bodies having a maximum range of 3 to 20 mm, e.g. 4 to 15 mm, particularly 5 to 12 mm. The maximum range is understood as the longest straight line between two points on the outer perimeter of the carrier.
[0157] The shape of the compressed body is not particularly limited and may be any technically feasible shape depending on the molding method, for example. For example, the carrier may be a solid tablet or a hollow tablet, such as a hollow cylinder. In a further embodiment, the carrier may be characterized by a multilobed structure. A multilobed structure is intended to refer to a cylinder structure having a number of cavities, such as grooves or flutes, extending from the periphery of the cylinder along the cylinder height. Generally, the cavities exist in an essentially equidistant arrangement around the circumference of the cylinder.
[0158] The compressive force during tableting affects the compression of the free-flowing feed mixture and, therefore, affects, for example, the density and / or mechanical stability of the compressed body. In practice, it has been found desirable to control the lateral fracture strength of the tableted catalyst carrier by selecting a suitable compressive force and to verify this by sampling. For the purposes of the present invention, the lateral fracture strength is the force that destroys the tableted catalyst carrier between two flat parallel plates, wherein the two flat parallel end faces of the catalyst carrier are perpendicular to the flat parallel plates.
[0159] To improve tablet compression characteristics, the free-flow feed mixture may undergo further processing, for example, by sieving, preheating, and / or pre-pelletization, i.e., pre-compression. For pre-pelletization, it is possible to use a roll compressor, for example, Fitzpatrick’s Chilsonator®.
[0160] Further information on tablet compression, particularly on pre-pelletization, sieving, lubricants, and molds, can be found in WO 2010 / 000720. For further information on tablet compression, refer to the Handbook of Powder Technology, Chapter 16: Tablet Compression, K. Pitt and C. Sinka, vol 11, 2007, pp. 735 to 778.
[0161] Advantageously, the tableting operation is performed as described in WO 2005 / 030393, DE 10 2008 040093 A1, DE 10 2008 040094 A1 and WO 2007 / 017431. The ambient temperature of the tablet press is typically 25°C. The particle diameter of the precursor composition to be compressed (of a finely divided, closely spaced dry mixture) is optionally in the range of 100 to 2000 μm, preferably 150 to 1500 μm, more preferably 400 to 1250 μm, or 400 to 1000 μm, or 400 to 800 μm, as a result of prior coarsening by compression (molding aids mixed prior to compression are not taken into account at this time).
[0162] Just as with the molding device used for compression or the molding method used therein, the desired shape of the molded body produced in the method of the present invention is not limited in any way.
[0163] A preferred ring shape (the shape of the uncalcined green body and the shape of the molded unsupported catalyst body resulting from calcination therefrom are typically essentially the same) is a shape of 5 mm x 5 mm x 2 mm (outer diameter x height (length) x inner diameter). This is because a fixed catalyst layer composed of rings of this shape results in a particularly small pressure drop for the reaction gas mixture flowing through the fixed catalyst layer (particularly in reaction tubes having an inner diameter of 22 mm to 30 mm). A small pressure drop is particularly advantageous when partial oxidation catalyzed by the fixed catalyst layer operates at a high space velocity of the reaction gas mixture on the fixed catalyst layer (at a high flow rate of the reaction gas mixture flowing through the fixed catalyst layer). Another preferred ring shape (which has advantageous bed characteristics, particularly in reaction tubes with a relatively small inner diameter (e.g., 20 mm)) is a shape of 5 mm x 3 mm x 2 mm (outer diameter x height (length) x inner diameter). Useful features are, of course, alternatively disclosed and recommended in WO 02 / 062737 and WO 2015 / 067656.
[0164] Particularly in the case of annularly formed precursor bodies (regardless of their shape, formed precursor bodies are also referred to as green bodies in the literature), forming compression advantageously results in the lateral fracture strength SDF of the generated formed body. v a (Refer to DE 10 2008 040093 A1, DE 10 2008 040094 A1 and WO 2005 / 030393) Relation 5 N ≤ SDF v ≤ 100 N, preferably 8 N ≤ SDF v ≤ 80 N, and more preferably 12 N ≤ SDF v It must be performed to satisfy ≤ 50 N.
[0165] The experimental determination of lateral fracture strength is carried out as described in WO 2005 / 030393 and WO 2007 / 017431. It will be understood that a ring-shaped green body, as recommended by DE 10 2008 040093 A1, is very particularly desirable according to the invention. In the manufacturing method described for the green body of the invention, the end faces of the annular or ring-shaped formed body may be flat (both or only one of the two end faces) or outwardly domed (curved) (convex) (in particular, see DE 10 2007 004961 A1, EP 0 184 790 A2, DE 10 2008 040093 A1 (e.g., paragraph
[0032] ) and DE 10 2008 04009 A1 (e.g., paragraph
[0074] ) and embodiments described in these documents in a form individualized to them). In determining / specifying the height of such geometrically formed body, such convex domed formation (curvature) is not generally considered in this document. A ring or annular molded body having convex dome-shaped (curved) end faces (preferably having both end faces with the same dome shape (curvature)) is advantageous in that a fixed catalyst layer of an annular or annular molded body having convex dome-shaped (curved) end faces (otherwise having the same shape) causes a lower pressure drop in the reaction gas mixture flowing through the fixed catalyst layer (particularly in the case of a fixed catalyst layer within a reaction tube) than a fixed catalyst layer of an annular or annular molded body having flat end faces. This applies particularly even when the ring shape is 5 mm x 5 mm x 2 mm (outer diameter (x) height (length) x inner diameter). The radius of this convex curvature is generally 0.4 to 5 times the outer diameter of the circular cylinder of the catalyst ring (e.g., 0.8 to 4 times, or 1.2 to 3 times, or 1.6 to 2.6 times).As previously mentioned, a fixed catalyst layer that causes a smaller pressure drop is particularly advantageous when partial oxidation catalyzed by the fixed catalyst layer operates at a high space velocity of the reaction gas mixture on the fixed catalyst layer (at a high flow rate of the reaction gas mixture flowing through the fixed catalyst layer).
[0166] A particularly advantageous ring shape of a molded body obtainable by compressing a finely divided precursor composition (finely divided, closely spaced dry mixture) is height ( H eight) / diameter( E The condition that external) = H / E = 0.3 to 1.5, or to 1.2 is satisfied. More preferably, H / E = 0.5 to 1.1 or 1.0. In addition, the I / E ratio (where I is ring-shaped) I It is advantageous for the annular or ring-shaped green body of the invention when the inner diameter is 0.3 to 1.5, preferably 0.6 to 1.1.
[0167] The aforementioned ring shape is particularly advantageous when it simultaneously possesses one of the favorable H / E ratios and one of the favorable I / E ratios. Such possible combinations are, for example, H / E = 0.3 to 1.5, or to 1.2 and I / E = 0.3 to 1.5, or 0.6 to 1.1. Alternatively, H / E may be 0.5 to 1.1, or to 1.0, and I / E may simultaneously be 0.3 to 1.5, or 0.6 to 1.1. Additionally, the relevant ring shape is advantageous when H is 2 to 7 mm, preferably 2 to 6 mm, or 3 to 6 mm. It is also advantageous when E in the ring is 4 to 8 mm, preferably 4 to 6 mm. The wall thickness of the preferred ring shape is 1 to 2 mm, or to 1.5 mm.
[0168] Accordingly, the possible ring shapes of the invention are (E x H x I) 5 mm x 5 mm x 2 mm, or 5 mm x 2 mm x 2 mm, or 5 mm x 3 mm x 2 mm, 5 mm x 5 mm x 2.5 mm, or 5 mm x 3 mm x 2.5 mm, or 5.5 mm x 5.5 mm x 2.5 mm, or 5.5 mm x 5.5 mm x 3 mm, or 5 mm x 3 mm x 3 mm, or 5.5 mm x 3 mm x 3.5 mm, or 6 mm x 3 mm x 4 mm, or 6 mm x 6 mm x 3 mm, or 6 mm x 6 mm x 3.5 mm, or 6.5 mm x 3 mm x 4.5 mm, or 7 mm x 3 mm x 5 mm, or 7 mm x 7 mm x 3 mm, or 7 mm x 3 mm x 4 mm, or 7 It is mm x 7 mm x 4 mm.
[0169] All figures regarding the specific surface area of solids in this document are, unless explicitly stated otherwise, determinations according to DIN 66131 (determination of the specific surface area of solids by gas adsorption (N2) according to Brunauer-Emmett-Teller (BET)).
[0170] In this document, all figures regarding total pore volume and the distribution of pore diameters relative to these total pore volumes refer to determinations made by the mercury porosimetry method using the AutoPore V 9600 (MicroActive Interactive Data Analysis Software) instrument of Micromeritics GmbH, D-52072 Aachen (bandwidth: 0.5 - 60,000, at 23°C) (evaluated by the Washburn equation using a mercury contact angle of 140° and a mercury surface tension of 480 mN / m = 480 dyn / cm). Here, the total pore volume refers to the total pore volume of pores having a diameter of > 0.03 to < 300 μm.
[0171] Advantageously according to the present invention, the molded precursor body has a minimum residual moisture content. This is especially true when a close mixing of various sources of non-oxygen elemental components occurs in a wet form (particularly when an aqueous mixture M is formed in this operation).
[0172] The residual moisture content of the advantageous green body preferably has a value of ≤ 10 wt%, more preferably ≤ 8 wt%, much more preferably ≤ 6 wt%, and optimally ≤ 4 wt% or ≤ 2 wt% (the residual moisture content can be determined as described in "Thermogravimetric Determination of Material Moisture Content", Fundamentals and Practical Applications, Horst Nagel, verlag moderne industrie (e.g., using the Computrac MAX 5000 XL from Arizona Instruments)).
[0173] If the green body is derived from an aqueous mixture M (so that its residual moisture content consists of water), the residual moisture content is determined by microwave (e.g., with BERTHOLD TECHNOLOGIES' LB 456 microwave system) to suit the purpose of application.
[0174] In this procedure, microwaves are irradiated onto the material to be investigated at a very low output (0.1 mW) (due to the relatively low output, the temperature of the material essentially does not undergo any change). As a result, the material components are polarized to different degrees. In the reaction, the microwaves lose speed and energy. At this point, the influence of water molecules is significantly greater than that of other components, which enables the selective determination of residual moisture content. This is because water molecules, considering their size and dipole characteristics, possess a particularly excellent ability to follow the alternating electromagnetic field in the microwave frequency range due to their dipole orientation. By doing so, they absorb energy and alter the alternating electromagnetic field through their electrical properties. This field attenuation and field alteration form the basis of the measurement principle. For example, it is possible to permanently analyze the resonance frequency of the sensor system by forming a weak microwave wave across the sensor area of a planar sensor and scanning the microwave frequency. As the moisture-containing material moves across the sensor, there is a shift in the resonance frequency and attenuation of its amplitude. With increasing water content, that is, with increasing bulk density of the measured substance, there is an increase in both attenuation and shift at the resonance frequency. However, the ratio of frequency shift to attenuation is a density-independent measure of the percentage moisture content and is therefore critical to the measurement of moisture content. This ratio represents the so-called microwave moisture measurement, which indicates the total moisture content. Since the microwave resonance method is an indirect moisture measurement method, calibration is required. In this calibration measurement, the sensor is used to measure a sample of substance with a defined moisture content. The relationship between the microwave moisture measurement and the corresponding defined absolute moisture content of the substance then forms the calibration of the measurement system. The measurement accuracy is typically ±0.1% moisture content (for example, moisture content can be determined using the Sartorius PMD300PA online moisture analyzer).
[0175] Against this background, spray drying of a wet (e.g., aqueous) mixture M must already be performed so that the resulting spray powder has a minimum residual moisture content.
[0176] Considering only the aspects mentioned, the green body must be stored with contact with ambient air (including air humidity) blocked as much as possible (preferably, storage is carried out under anhydrous inert gas or pre-dried air or in an airtight container until calcination occurs).
[0177] The formation / molding and storage of finely divided, close-dry mixtures are already advantageously carried out in a state where ambient air (including air humidity) is blocked (e.g., under an N2 atmosphere).
[0178] The green body is typically calcined at a temperature (calcination temperature) that reaches or generally exceeds at least 350°C. However, the temperature of 650°C is not typically exceeded during the calcination process (in this document, the term “calcination temperature” refers to the temperature present in the calcination material (the calcination material has a very uniform calcination temperature; this is correspondingly true for other calcination conditions)). Advantageously, the temperature of 600°C, preferably 570°C, and frequently 550°C is not exceeded during the calcination process. Furthermore, during the calcination process, the temperature of 380°C is preferably exceeded, 400°C, particularly advantageously 420°C, and very preferably 440°C. The calcination may also be subdivided into a number of sections over the period.
[0179] Calcination is advantageously preceded by thermal pretreatment at temperatures ≥ 120°C and < 350°C, preferably ≥ 150°C and ≤ 320°C, more preferably ≥ 170°C and ≤ 290°C. Suitable for the intended application, this thermal pretreatment is performed until the component present in the composition to be heat-treated and decomposing into a gaseous compound under the conditions of heat treatment is mostly (preferably completely) decomposed to produce a gaseous compound (the time required for this may be, for example, 3 to 15 hours, frequently 4 to 10 hours, or 5 to 8 hours). This is because, first, the molar amount of cations other than metal ions present in the composition to be subsequently calcined is ≤ 20 mol% (preferably ≤ 10 mol%) based on the total molar amount of cations present, and second, O present in the same composition 2- This generally applies when the molar amount of the other anions is ≤ 20 mol% (preferably ≤ 10 mol%) based on the total molar amount of the anions present.
[0180] Accordingly, the favorable temperature window for the final calcination temperature is within a temperature range of 400 to 600°C, or preferably within a temperature range of 420 to 570°C, or more preferably within a temperature range of 450 to 550°C.
[0181] The total calcination time generally exceeds 0.5 hours and frequently exceeds 2 hours. Typically, the processing time for calcination is not exceeded by 45 hours or 30 hours. The total calcination time is often less than 25 hours. In principle, shorter calcination times are generally sufficient at higher calcination temperatures than at lower calcination temperatures. In one embodiment of calcination advantageous to the invention, 550°C is not exceeded, and the calcination time in a temperature window of ≥ 430°C and ≤ 550°C is 4 hours to ≤ 25 hours.
[0182] The entire heat treatment (including the decomposition phase) of the precursor composition (e.g., green body) may be performed under an inert gas or an oxidizing atmosphere, e.g., air (or other mixtures of inert gas and molecular oxygen), and under a reducing atmosphere (e.g., a mixture of inert gas, NH3, CO, and / or H2, or under methane). The heat treatment may also be performed under reduced pressure. The atmosphere may also be changed throughout the course of the heat treatment.
[0183] Heat treatment (particularly the calcination phase) is preferably carried out in an oxidizing atmosphere. Suitable for the application period, this atmosphere consists mainly of stagnant air or (preferably) flowing air (more preferably, an air stream flows through the composition (calcined material) to be heat treated). However, the oxidizing atmosphere may likewise consist of a stationary or moving mixture of, for example, 25 volume% N2 and 75 volume% air, or 50 volume% N2 and 50 volume% air, or 75 volume% N2 and 25 volume% air (a treatment atmosphere consisting of 100 volume% N2 is also possible).
[0184] In principle, the heat treatment (e.g., calcination) of a precursor composition (e.g., green body) may be performed in various oven types, for example, in a heatable air circulation chamber (air circulation oven, e.g., air circulation shaft oven), a step oven, a rotary oven, a belt calciner, or a shaft oven. Advantageously according to the invention, the heat treatment (e.g., calcination) is performed in a belt calciner device as recommended by DE 100 46 957 A1 and WO 02 / 24620. The formation of hot spots within the material to be treated (within the calcined material) is very substantially prevented in this case, in that an elevated volumetric flow rate of the calcination atmosphere is conveyed through the calcined material on a gas-permeable conveyor belt supporting the calcined material using a fan (these ensure very substantial homogeneity of the calcination temperature within the calcined material).
[0185] In the heat treatment of the precursor composition (e.g., green body) to be performed as described, the molding aid used may be retained in the formed molded catalyst body, or at least partially escaped from it in gaseous form to produce gaseous compounds (e.g., CO, CO2) as a result of thermal and / or chemical decomposition. The molding aid remaining in the molded catalyst body essentially exhibits only a diluting effect on the active composition during the process of its catalytic use. In principle, the heat treatment in this regard may be performed as described in US 2005 / 0131253.
[0186] Typically, the lateral fracture strength of an annularly molded unsupported catalyst body that can be obtained as described according to the present invention is 4 to 16 N, frequently 5 to 14 N or 6 to 12 N.
[0187] The specific (BET) surface area of the molded unsupported catalyst body is advantageously 2 to 20 m² 2 / g or 15 m 2 / g, preferably 3 to 10 m2 / g and more preferably 4 to 8 m 2 / g. Advantageously according to the invention, the corresponding total pore volume (mercury porosity measurement) is 0.33 to 0.60 cm³. 3 In the range of / g, preferably 0.36 to 0.54 cm 3 In the range of / g, and more preferably 0.38 to 0.50 cm 3 It is in the range of / g.
[0188] Plot pore diameter in μm units on the x-axis and cm 3 cm of each pore diameter relative to the total pore volume in units of / g 3 When the logarithm of the differential contribution in units of / g is plotted on the y-axis, the molded unsupported catalyst body, which is particularly advantageous according to the present invention, generally exhibits an essentially unimodal distribution (having only a single distinct maximum). The contribution to the total pore volume of pores having a pore radius of ≤ 0.1 μm is ≤ 0.05 cm 3 If / g, the result is particularly excellent overall target product selectivity, for example, in the case of heterogeneous catalytic partial oxidation of propene to acrolein and / or acrylic acid. The contribution of these relatively narrow pores to the total pore volume is > 0.05 cm 3 If / g, an increase in calcination time and / or calcination temperature may cause a reduction in this contribution which is advantageous according to the invention.
[0189] Furthermore, for increased overall target product selectivity, it was found that the contribution to the total pore volume of pores having a pore radius in the range of 0.1 to 1 μm is 85% to 99% by volume, advantageously 87% to 97% by volume, and more preferably 89% to 95% by volume, based on the total pore volume.
[0190] It will be understood that the molded unsupported catalyst body may be diluted with an inert material and used for catalytic action in heterogeneous partial gas-phase oxidation. Suitable inert diluent materials of this kind include elemental oxides that are calcined at high temperatures and thus have a relatively low level of pores, such as aluminum oxide, silicon dioxide, thorium dioxide, and zirconium dioxide. Alternatively, finely divided silicates, such as finely divided silicon carbide or magnesium silicate and aluminum silicate or steatite, may be used for the aforementioned purposes. Advantageously, the procedure for the purpose of application is, for example, to grind the calcined active composition into a fine powder. This is then mixed with the finely divided diluent material, and the resulting mixed powder is formed into a molded geometric body (preferably by tableting) using the molding method presented in this document. By subsequently calcining it once again, this body is then transformed into a corresponding molded unsupported catalyst body. However, the finely divided inert diluent material may, of course, already be incorporated into a wet (e.g., aqueous) mixture M before, for example, drying. Additionally, the finely divided inert diluent material may be incorporated into a finely divided dry mixture. However, according to the invention, such a procedure is relatively undesirable.
[0191] A special feature of the molded unsupported catalyst bodies produced by the described advantageous manufacturing method is that they essentially do not possess local centers of elemental oxides. Instead, these elements are a very substantial part of a complex mixed oxomolybdate containing Bi, Fe, and Mo. This has been found to be advantageous with respect to the objective of the invention of minimizing the complete combustion of undesirable organic reaction gas mixture components according to the present invention during the process of the related heterogeneous catalytic partial oxidation.
[0192] Otherwise, the procedure for manufacturing unsupported catalysts is appropriate as in WO 2010 / 066645 in terms of maximum efficiency of material utilization.
[0193] The molded unsupported catalyst body of the present invention is suitable for catalytic heterogeneous catalytic partial oxidation of propene to acrolein, as well as for catalytic heterogeneous catalytic partial gas phase oxidation of alkanes, alkanols, alkenes and / or alkenals having 3 to 6 carbon atoms (in this document, partial oxidation should be understood to mean such reaction of an organic compound having reactive involvement of molecular oxygen, which includes at least one additional oxygen atom in a chemically bonded form after the reaction is completed and before the performance of partial oxidation). In this document, the term “partial oxidation” should alternatively include oxidative dehydrogenation and partial ammonia oxidation, i.e., partial oxidation in the presence of ammonia.
[0194] The molded unsupported catalyst body of the present invention is particularly suitable for catalytic action of heterogeneous catalytic partial gas phase oxidation of propene to acrolein and isobutene to methacrolein, and for catalytic action of heterogeneous catalytic partial gas phase ammonia oxidation of propene to acrylonitrile and isobutene to methacrylonitrile.
[0195] As mentioned above, the heterogeneous catalytic partial gas phase oxidation of propene (isobutene and / or tert-butanol) to acrolein (methacrylate) forms the first step of the two-stage heterogeneous catalytic partial gas phase oxidation of propene (isobutene and / or tert-butanol) to acrylic acid (methacrylic acid), as described, for example, in WO 2006 / 42459.
[0196] Therefore, the formation of acrylic acid (methacrylic acid) byproducts associated with the heterogeneous catalytic partial gas phase oxidation of propene (isobutene) to acrolein (methacrylatein) is generally not undesirable and is typically included by the formation of the desired target product.
[0197] The above description is particularly applicable to the annularly molded unsupported catalyst body of the invention.
[0198] Heterogeneous catalytic partial oxidation (partially that of propene to acrolein), for example, regarding similar catalysts, documentation DE 10 2007 004961 A1, WO 02 / 49757, WO 02 / 24620, DE 10 2008 040093 A1, WO 2005 / 030393, EP 0 575 897 A1, WO 2007 / 082827, WO 2005 / 113127, WO 2005 / 047224, WO 2005 / 042459, WO 2007 / 017431, DE 10 2008 042060 A1, WO 2008 / 087116, DE 10 2010 048405 A1, DE 10 It may be carried out as described in 2009 047291 A1, DE 10 2008 042064 A1, DE 10 2008 042061 A1, WO 2015 / 067656 and DE 10 2008 040094 A1 (more specifically, it is possible to proceed in a manner corresponding to the exemplary embodiments of these documents).
[0199] However, the advantageous properties of the molded unsupported catalyst body (particularly cyclic) obtainable as described exist even when the space velocity of the catalyst pack for a reactor having propene, isobutene, and / or tert-butanol (or its methyl ether) included in the reaction gas input mixture is ≥ 130 L(STP) / L (catalyst feed)·h, or ≥ 140 L(STP) / L·h, or ≥ 150 L(STP) / L·h, or ≥ 160 L(STP) / L·h (for the purpose of space velocity consideration in this document, the upstream and / or downstream bed of pure inert material is not considered as part of the catalyst pack; the volume of the catalyst pack (fixed catalyst bed) is, incidentally, its bulk volume located in the reactor). Typically, the aforementioned space velocity of the catalyst pack will be ≤ 600 L(STP) / L·h, frequently ≤ 500 L(STP) / L·h, and in many cases ≤ 400 L(STP) / L·h or ≤ 350 L(STP) / L·h. Space velocities in the range from ≥ 160 L(STP) / L·h or ≥ 180 L(STP) / L·h to ≤ 300 or ≤ 250 or ≤ 200 L(STP) / L·h are particularly suitable.
[0200] In this document, the space velocity of the reaction gas input mixture on the fixed catalyst bed is understood to mean the amount of the reaction gas input mixture supplied to the fixed catalyst bed in standard liters (= L (standard temperature / pressure); the volume in liters that the corresponding amount of the reaction gas input mixture would occupy under standard conditions of 0°C and 1 atm abs (1.01 bar)), which is per hour relative to the volume of the bed (excluding the bed section of pure inert material), i.e., the bed volume (-> unit = L(STP) / L·h). In this document, L (standard temperature / pressure) or m 3 Units of standard volume, such as (standard temperature and pressure), are always associated with standard conditions of 0°C and 1 atm abs (1.01 bar) (unless explicitly stated otherwise).
[0201] The space velocity can also be based on only one component of the reaction gas input mixture (e.g., only the organic starting compound to be partially oxidized). In that case, it is the volume of this component (e.g., the organic starting compound to be partially oxidized) supplied to the fixed catalyst bed (the catalyst charge of the reactor) per hour, based on the volume of its bed.
[0202] Of course, the molded unsupported catalyst body (e.g., cyclic) obtainable according to the invention as a catalyst for the partial oxidation of propene to acrolein or of isobutene and / or tert-butanol (or its methyl ether) to methacrolein can also be operated in an advantageous manner according to the invention at catalyst-filled space velocities having a starting compound for partial oxidation of ≤ 130 L(STP) / L·h, or ≤ 120 L(STP) / L·h, or ≤ 110 L(STP) / L·h, or ≤ 100 L(STP) / L·h, or ≤ 90 L(STP) / L·h. However, generally, this space velocity will be at a value of ≥ 20 L(STP) / L·h, or ≥ 30 L(STP) / L·h, or ≥ 40 L(STP) / L·h, or ≥ 50 L(STP) / L·h, or ≥ 60 L(STP) / L·h, or ≥ 70 L(STP) / L·h, or ≥ 80 L(STP) / L·h.
[0203] In principle, the space velocity of the catalyst charge (fixed catalyst bed) of a reactor having a starting compound for partial oxidation (propene, isobutene, and / or tert-butanol (or its methyl ether)) can be adjusted using two adjustment variables:
[0204] a) the space velocity of the reaction gas input mixture (reaction gas mixture supplied to the fixed catalyst bed) on the catalyst packing, and / or
[0205] b) Content of the starting compound for partial oxidation in the reaction gas input mixture.
[0206] A molded unsupported catalyst body (e.g., in an annular form) obtainable according to the present invention is particularly suitable when the space velocity of an organic compound for partial oxidation on a catalyst pack exceeds 130 L (STP) / L·h, and the space velocity is particularly controlled through the control variable a).
[0207] As a general rule, for example, the propene content (isobutene content or tert-butanol content (or methyl ether content)) in the reaction gas input mixture will be 4% to 10 volume%, frequently 5% to 9 volume%, or 5.5% to 8.0 volume%, or 6.0% to 7.5 volume%, essentially independent of the space velocity on the catalyst pack (in each case, based on the total volume (flow rate) of the reaction gas input mixture flowing into the fixed catalyst bed).
[0208] Often, the gas phase partial oxidation method of partial oxidation catalyzed by a molded (e.g., cyclic) unsupported catalyst body of the invention, which can be obtained as described, will be carried out in a volume ratio of (organic) compound (e.g., propene): oxygen: inert (non-reactive) gas (including vapor) for partial oxidation of 1:(1.0 to 3.0):(5 to 25), preferably 1:(1.5 to 2.3):(10 to 20), in a reaction gas input mixture (essentially independent of space velocity).
[0209] At this time, the inert gas is understood to mean a gas that remains chemically unchanged in a single pass of the reaction gas mixture through the catalyst layer during the process of partial oxidation, up to a range of at least 95 mol%, preferably up to a range of at least 98 mol%.
[0210] In the reaction gas input mixture described above, the inert gas may consist of molecular nitrogen up to a range of ≥ 20 volume%, or up to a range of ≥ 30 volume%, or up to a range of ≥ 40 volume%, or up to a range of ≥ 50 volume%, or up to a range of ≥ 60 volume%, or up to a range of ≥ 70 volume%, or up to a range of ≥ 80 volume%, or up to a range of ≥ 90 volume%, or up to a range of ≥ 95 volume%.
[0211] However, at higher space velocities of the organic compound to be partially oxidized on the catalyst pack of the reactor (e.g., ≥ 150 L(STP) / L·h), the additional use of diluent gases having relatively high molar heat capacity and / or thermal conductivity, such as propane, ethane, methane, pentane, butane, CO2, CO, vapor, and / or inert gases, is recommended (but not mandatory) for the reaction gas input mixture. Generally, these gases and mixtures thereof may also be used at lower space velocities of the organic compound to be partially oxidized on the catalyst pack. A cycle gas may also be used as a partially diluent gas. A cycle gas is understood to refer to the tail gas remaining when the target compound is essentially selectively separated from the product gas mixture of partial oxidation. It should be taken into account that the partial oxidation to acrolein or methacrolein using a molded, unsupported catalyst body, for example, in a cyclic form, which can be obtained according to the invention, may be only the first step of a two-stage partial oxidation to acrylic acid or methacryl acid as the actual target compound, and thus the circulating gas is then typically formed only after the second step (a typical circulating gas composition in the case of heterogeneous catalytic partial oxidation of propene to acrolein and / or acrylic acid is shown in paragraphs
[0063] and
[0075] of DE 102 32 482 A1). In the context of such two-stage partial oxidation, the product gas mixture of the first step is fed as is, optionally after cooling and / or secondary oxygen addition (usually as air), generally to the second partial oxidation step.
[0212] When partially oxidizing propene to acrolein using the molded unsupported catalyst body of the invention obtainable as described (e.g., in a cyclic form), the typical composition of the reaction gas input mixture measured at the reactor inlet may include, for example, the following components (regardless of the selected space velocity):
[0213] Propene 6 to 6.5 volume%,
[0214] H2O 1 to 3.5 volume%,
[0215] CO x 0.8 to 1.7 volume%,
[0216] Acrolein 0.015 to 0.04 volume%,
[0217] oxygen , 9.4 to 12.3 volume% and
[0218] Total 100% by volume with the remaining molecular nitrogen;
[0219] or
[0220] Propene 5.6% by volume,
[0221] H2O 1.4 volume%,
[0222] CO x 1.2 volume%,
[0223] Oxygen 10.2 volume%, and
[0224] The remaining molecules are nitrogen, totaling 100% by volume.
[0225] The former composition is particularly suitable at propene space rates of ≥ 130 L(STP) / L·h, whereas the latter composition is particularly suitable on a fixed catalyst layer (e.g., for initiating partial oxidation) at propene space rates of < 130 L(STP) / L·h, especially ≤ 100 L(STP) / L·h.
[0226] Alternatively, for the partial oxidation of propene to acrolein according to the present invention, it is also possible to use a reaction gas injection mixture of a composition according to Example 1 of EP 0 990 636 A1, or according to Example 2 of EP 0 990 636 A1, or according to Example 3 of EP 1 106 598 A2, or according to Example 26 of EP 1 106 598 A2, or according to Example 53 of EP 1 106 598 A2, or according to an example of WO 2021 / 013640.
[0227] The molded unsupported catalyst body of the invention obtainable as described is also suitable for the method of DE 102 46 119 A1 or DE 102 45 585 A1, for example in an annular form.
[0228] The reaction temperature for heterogeneous catalytic partial oxidation of propene to acrolein according to the present invention is often 300 to 450°C, or up to 400°C, or up to 380°C, when using the molded unsupported catalyst body of the invention (e.g., cyclic) available as described. A particularly preferred reaction temperature window is 305 to 345°C. The same applies to methacrolein as the target compound.
[0229] The reaction pressure for the aforementioned partial oxidation is generally 0.5 to 4 or 3 barg, or preferably 1.1 or 1.5 to 4 or 3 barg (in this document, unless otherwise explicitly stated, the meaning is always absolute pressure).
[0230] In the aforementioned partial oxidation of the present invention, the total space velocity of the reaction gas input mixture on the catalyst packing typically reaches 1,000 to 10,000 L(STP) / L·h, usually 1,500 to 5,000 L(STP) / L·h, and often 2,000 to 4,000 L(STP) / L·h.
[0231] Propenes useful for use in reaction gas input mixtures are, for example, polymer grade propene and chemical grade propene as described in WO 2004 / 007405.
[0232] The oxygen source used is typically air (optional, including circulating gas).
[0233] Partial oxidation using a molded unsupported catalyst body obtainable as described (e.g., annular molded unsupported catalyst body) can be carried out in the simplest case, for example, in a single-zone shell and tube reactor as described by DE 44 31 957 A1, EP 0 700 714 A1 and EP 0 700 893 A1.
[0234] Conventionally, in the shell and tube reactors described above, the catalyst tubes are made of ferritic steel and typically have a wall thickness of 1 to 3 mm. Their inner diameter is generally 20 to 30 mm, often 21 to 26 mm. Typical catalyst tube lengths are, for example, 3.50 m, 4.00 m, or 4.50 m. The number of catalyst tubes accommodated in the shell and tube vessel is usefully at least 1,000, preferably at least 5,000. Frequently, the number of catalyst tubes accommodated in the reaction vessel is 15,000 to 40,000. Shell and tube reactors having a number of catalyst tubes exceeding 45,000 are exceptional. Within the vessel, the catalyst tubes are typically arranged in a uniform distribution, and the distribution is appropriately selected so that the separation of the center inner axes of adjacent catalyst tubes (called the catalyst tube pitch) is 35 to 45 mm (Ref. EP 0 468 290 B1).
[0235] Partial oxidation may alternatively be performed in a multi-zone (e.g., "2-zone") shell and tube reactor, as recommended by DE 199 10 506 A1, DE 103 13 213 A1, DE 103 13 208 A1 and EP 1 106 598 A2, particularly at an elevated space velocity of the organic compound to be partially oxidized on the catalyst packing of the shell and tube reactor. For a 2-zone shell and tube reactor, typical catalyst tube lengths are 3.50 m, 4.00 m, or 4.50 m. All other details are essentially the same as those described for a single-zone shell and tube reactor. In each temperature control zone of the single-zone or multi-zone shell and tube reactor (a single-zone shell and tube reactor has only one temperature control zone), a heat exchange medium is passed around the catalyst tube where the catalyst packing (fixed catalyst layer) is present. Suitable examples of heat exchange media include melts of salts such as potassium nitrate, potassium nitrite, sodium nitrite and / or sodium nitrate, or melts of low-melting point metals such as alloys of sodium, mercury and other metals. The flow rate of the heat exchange media within each temperature control zone is generally selected so that the temperature of the heat exchange media rises from the inlet point of the temperature control zone to the outlet point of the temperature control zone by 0 to 15°C, frequently by 1 to 10°C, or by 2 to 8°C, or by 3 to 6°C.
[0236] When viewed across each temperature control zone, the inlet temperature of the heat exchange medium, which can be guided in parallel or counterflow with respect to the reaction gas mixture, is preferably selected as recommended in documents EP 1 106 598 A2, DE 199 48 523 A1, DE 199 48 248 A1, DE 103 13 209 A1, EP 0 700 714 A1, DE 103 13 208 A1, DE 103 13 213 A1, WO 00 / 53557, WO 00 / 53558, WO 01 / 36364, WO 00 / 53557 and other documents cited as prior art in these documents. Within the temperature control zone, the heat exchange medium is preferably guided in a meandering manner. When considered over a length section of the temperature control zone containing a catalytically active section of the fixed catalyst bed (not a purely inert bed), the difference between the highest and lowest temperatures of the heat exchange medium within the temperature control zone should advantageously be ≥ 0°C and ≤ 5°C (this difference is preferably small). Generally, shell and tube reactors additionally have a thermal tube to determine the temperature of the reaction gas in the catalyst bed (the thermal tube and the reaction tube are filled with the same fixed bed). In an appropriate manner, the inner diameter of the thermal tube and the diameter of the receiving well (thermowell) for the thermocouple centered therein and extending parallel to the long axis of the thermal tube are selected such that the ratio of the volume to the heat-removal surface area generating the heat of the reaction in the thermal tube and the working tube is the same or only slightly different.
[0237] For the working tube and the heat tube, the pressure drop must be equal based on the same gas hourly space velocity (GHSV) (= the volumetric flow rate of the reaction gas mixture entering the tube divided by the bed volume of the fixed catalyst layer present in the tube). Compensation for the pressure drop in the heat tube may be achieved, for example, by adding catalyst spall to the molded unsupported catalyst body. This compensation is appropriately and uniformly applied over the entire length of the heat tube. The filling of the heat tube may otherwise be configured as described in EP 0 873 783 A1.
[0238] To provide a catalyst filler within a catalyst tube, a single molded unsupported catalyst body (e.g., in an annular form) obtainable as previously mentioned or described may be used, or a largely homogeneous mixture of a molded unsupported catalyst body (e.g., in annular form) obtainable as described, for example, and a molded body that is essentially inert to heterogeneous partial catalytic vapor oxidation without containing an active composition may be used. Useful materials for such inert molded bodies include, for example, porous or non-porous aluminum oxide, silicates such as silicon dioxide, zirconium dioxide, silicon carbide, magnesium or aluminum silicate, and / or steatite (an example of the C220 type of CeramTec, DE).
[0239] The shape of these inert molded diluent bodies is as desired. This means that they can be, for example, spheres, polygons, solid cylinders, or—as in the case of annular molded catalyst bodies—rings. Frequently, the inert molded diluent bodies selected will have shapes corresponding to the shape of the molded catalyst body to be diluted with them. However, depending on the catalyst filler, the shape of the molded catalyst body may also be changed, or molded catalyst bodies of different shapes may be used as a generally homogeneous blend. In a relatively less desirable procedure, the active composition of the molded catalyst body may also be changed depending on the catalyst filler.
[0240] More generally, the catalyst pack is configured such that the volume-specific activity (i.e., a value normalized to a unit volume) is advantageously maintained constant or increased (continuously, discontinuously, or in steps) in the flow direction of the reaction gas mixture.
[0241] A reduction in activity per volume can be achieved in a simple manner, for example, by uniformly diluting a base amount of a molded unsupported catalyst body (e.g., in an annular form) uniformly prepared according to the present invention with an inert molded diluent body. The higher the proportion of the selected molded diluent body, the smaller the amount of active composition or catalytic activity present in a specific volume of the packing. However, the reduction can also be achieved by changing the shape of the molded unsupported catalyst body obtainable according to the invention in such a way that the amount of active composition present in a unit volume inside the reaction tube becomes smaller.
[0242] In the case of heterogeneous catalytic gas phase partial oxidation using a molded unsupported catalyst body (e.g., annular shape) obtainable as described, the catalyst packing is preferably uniformly composed of only one type of molded unsupported catalyst body over its entire length, or is structured as follows. At the reactor inlet, an essentially homogeneous mixture of a molded unsupported catalyst body (e.g., in an annular shape) and an inert molded diluent body (both preferably having essentially the same shape) is positioned over a length of 10% to 60%, preferably 10% to 50%, more preferably 20% to 40%, and very preferably 25% to 35% of the total length of each of the catalyst packs (i.e., over a length of 0.70 to 1.50 m, preferably 0.90 to 1.20 m), wherein the proportion by weight of the molded diluent body (where the bulk densities of the molded catalyst body and the molded diluent body are generally only slightly different) is typically 5% to 40% by weight, or 10% to 40% by weight, or 20% to 40% by weight, or 25% to 35% by weight. This first packing section is advantageously followed by a bed of the same molded unsupported catalyst body (e.g., annular shape) obtainable as described (than in the first section), diluted to only a lesser degree, up to the end of the length of the catalyst packing (i.e., over a length of 1.00 to 3.00 m or 1.00 to 2.70 m, preferably 1.40 to 3.00 m, or 2.00 to 3.00 m), or, very preferably, a 100% (undiluted) bed of the same molded unsupported catalyst body (e.g., annular shape) used in the first section is followed. It is also possible to select a constant dilution over the entire packing during the process.It is also possible to fill the first section with a molded unsupported catalyst body (e.g., annular shape) having a low active composition density based only on its space occupation, and fill the second section with a molded unsupported catalyst body (e.g., annular shape) obtainable according to the invention having a high active composition density based on its space occupation (e.g., 6.5 mm x 3 mm x 4.5 mm [outer diameter (x) height x inner diameter] in the first section, and 5 x 2 x 2 mm [E x H x I] in the second section).
[0243] A bed of an inert molded body may be positioned upstream of the actual fixed-bed catalyst pack in the flow direction of the reaction gas mixture, and the purpose of this is, for example, to increase the entry temperature of the reaction gas mixture to the temperature of the heat exchange medium.
[0244] Furthermore, in accordance with the teachings of the prior art (e.g., WO 2012 / 049246), when heterogeneous catalytic partial oxidation of propene to acrolein (or in the case of heterogeneous catalytic partial oxidation for the production of methacrolein), the catalyst charge of the reactor (especially a fresh catalyst charge) and the method conditions for catalytic partial oxidation are preferably selected (configured) such that, in the partial oxidation operation, there is no point within the fixed catalyst charge where the difference between the temperature of the fixed catalyst charge at this point and the temperature of the heat exchange medium at this point level is ≥ 120°C. Advantageously, however, at all points, this temperature difference is ≤ 100°C (particularly 40 to 100°C) in the positive direction, and particularly advantageously ≤ 90°C (particularly 50 to 90°C). In principle, however, such (positive) temperature difference may also be ≤ 50°C or ≤ 40°C. Additionally, the configuration is preferably such that when the temperature of the heat exchange medium is increased by 1°C, this temperature difference rises by > 0°C but ≤ +9°C, more preferably ≤ +7°C, preferably ≤ +5°C, and even more preferably ≤ +3°C at any point within the fixed catalyst layer (see also EP 1 106 598 A1).
[0245] Otherwise, heterogeneous catalytic partial oxidation for the production of acrolein (from propene) or methacrolein (from the C4 precursor compound mentioned in this document) using a cyclic molded unsupported catalyst body prepared according to the present invention can be advantageously carried out in a manner fully corresponding to the details of WO 2015 / 067656.
[0246] In general, for partial oxidation for the production of acrolein or methacrolein carried out using a molded, unsupported catalyst body (e.g., in a cyclic form) obtainable as described, as a catalyst, the catalyst charge, starting reaction gas mixture, space velocity, and reaction temperature are generally selected such that in a single pass of the reaction gas mixture through the catalyst charge, the conversion of the organic compound to be partially oxidized (propene, isobutene, tert-butanol, or its methyl ether) is at least 90 mol%, or at least 92 mol%, preferably at least 93 mol% or at least 94 mol%, or at least 95 mol% or at least 97 mol%, but typically ≤ 99 mol%. At this time, the selectivity for the target product (total of acrolein and acrylic acid or total of methacrolein and methacrylic acid) will regularly be ≥ 80 mol%, or ≥ 85 mol% or ≥ 90 mol%.
[0247] Finally, it should be noted that the molded unsupported catalyst body of the invention, obtainable as described, also has advantageous fracture characteristics in reactor charging.
[0248] The initiation of a fresh catalyst filler (fixed catalyst layer) comprising a molded unsupported catalyst body (e.g., in an annular form) obtainable according to the present invention can be performed, for example, as described in DE 103 37 788 A1 or DE 10 2009 047291 A1.
[0249] The formation of the molded unsupported catalyst body obtainable according to the present invention can be accelerated by carrying out an essentially constant conversion at an elevated space velocity of the reaction gas input mixture on the catalyst filler.
[0250] In addition, the unsupported catalyst obtainable according to the present invention is generally suitable for catalytic action of gas phase portion (dark)oxidation converting alkanols, alkanals, alkenes, alkanes, and alkenals having 3 to 6 (i.e., 3, 4, 5, or 6) carbon atoms into olefinic unsaturated aldehydes and / or carboxylic acids (and corresponding nitriles), and for oxidative dehydrogenation under gas phase catalysis of the aforementioned organic compounds having 3, 4, 5, or 6 carbon atoms.
[0251] Industrial-scale manufacturing of the molded unsupported catalyst body of the present invention is appropriately carried out in a manner similar to that described in DE 10 2008 040093 A1 and DE 10 2008 040094 A1 (particularly advantageously as in the exemplary embodiments of these documents).
[0252] Examples
[0253] Preparation of molded unsupported catalyst bodies (K1 to K13):
[0254] Active multimetal oxide is Mo 12 Bi 0.6 Fe3Co 4.9 Ni 2.6 K 0.12 O x Preparation of a molded unsupported catalyst body (K1) having the stoichiometry of
[0255] The stirring vessels used were each filled in the presence of ambient air. During the stirring / mixing process, they were hermetically sealed with lids having pressure-releasing valves for the atmosphere (1 atm abs, 1.01 bar abs).
[0256] a) Preparation of aqueous solution B
[0257] 3.9 kg of demineralized water was initially added to a temperature-controlled stainless steel (EN 1.4541) cylindrical stirring vessel (capacity 10 L) equipped with an anchor stirrer, and heated to 60°C while stirring (150 rpm).
[0258] Next, 23.5 g of a 47 wt% potassium hydroxide aqueous solution (KOH 47 wt%) at a temperature of 20°C was added with constant stirring and while maintaining the temperature at 60°C. 1161 g of fine-particle ammonium heptamolybdate tetrahydrate (Mo 54.3 wt%, supplier: NIPPON INORGANIC COLOUR & CHEMICAL CO., LTD., 3-14-1 Funado Itabashi-ku Tokyo 174-0041(JP); turbidity determined according to WO 2016 / 147324 was 219 NTU) was added in portions with stirring at a temperature of 25°C while maintaining the temperature at 60°C with constant stirring, and the resulting aqueous solution (which was slightly turbid as a result of a minimal amount of insoluble isopolymolybdate contaminants) was stirred (150 rpm) for an additional 20 minutes at 60°C.
[0259] b) Preparation of aqueous solution A
[0260] In a temperature-controlled stainless steel (EN 1.4541) cylindrical stirring vessel (capacity 5 L) equipped with an anchor stirrer, initially 3765 g of an aqueous cobalt(II) nitrate solution (Co 12.6 wt%, nitrate (NO3)) in nitric acid -27 wt%, cobalt metal from MFT Metals & Ferro-Alloys Trading GmbH, D-41474 Viersen, with purity > 99.6 wt%, Ni < 0.3 wt%, Fe < 100 mg / kg, Cu < 50 mg / kg dissolved in aqueous nitric acid) was added, and the mixture was heated to 60°C while stirring (150 rpm). Under continuous stirring (150 rpm) and continuous heating to 60°C, 1994 g of molten iron(III) nitrate citric acid (Fe 13.8 wt%, alkali metal < 0.4 wt%, chloride < 0.01 wt%, sulfate < 0.02 wt%, from Dr. Paul Lohmann GmbH, D-81857 Emmerthal) was metered in at 60°C and the mixture was stirred (150 rpm) for an additional 10 minutes at 60°C.
[0261] To the resulting aqueous solution, an aqueous bismuth nitrate solution (Bi 11.1 wt%, nitrate (NO3)) in 1856 g of nitric acid at 60°C. - ) 13 wt%, bismuth metal of Sidech SA, BE-1495 Tilly, Bi purity > 99.997 wt%, Pb < 7 mg / kg, Ni, Ag, Fe each < 5 mg / kg, Cu, Sb each < 3 mg / kg, and Cd, Zn each < 1 mg / kg were dissolved in aqueous nitric acid) was added, and the mixture was then stirred (150 rpm) for an additional 10 minutes at 60°C.
[0262] To the resulting aqueous solution, 1817 g of aqueous nickel nitrate solution in nitric acid (13.8 wt% Ni, 0.6 wt% Free nitric acid, prepared by dissolving nickel metal in aqueous nitric acid) was added at 60°C, and the mixture was then stirred (150 rpm) for an additional 10 minutes at 60°C.
[0263] c) Mix aqueous solution A and aqueous solution B to produce an aqueous mixture M
[0264] Aqueous solution A at 60°C was continuously metered into aqueous solution B at 60°C within 15 minutes using a peristaltic pump (Type: BVP, Company: Ismatec SA, Labortechnik-Analytik, Feldeggstraße 6, CH-8152 Glattbrugg, Setting: 320 scale division), at which time aqueous solution B was vigorously stirred with an Ultra-Turrax (Janke & Kunkel GmbH & Co. KG - IKA-Labortechnik, Janke & Kunkel-Str. 10, DE-79219 Staufen, Shaft type: 550KR-G45 fine, Shaft tube diameter: 25 mm, Stator diameter: 45 mm, Rotor diameter: 40 mm, Setting: Level (5)). Aqueous solution A was introduced at the level of the rotor of the Ultra-Turrax stirrer, offset by about 0.5 to 1 cm from the outer edge of the rotor of the Ultra-Turrax stirrer. The resulting aqueous suspension was stirred at 60°C for an additional 15 minutes.
[0265] d) Spray drying of aqueous mixture M
[0266] Aqueous mixture M was spray-dried immediately after preparation. Each aqueous mixture (suspension) M (continuously stirred during spray-drying) that was continuously stirred at 60°C by an anchor stirrer (150 rpm) was spray-dried in parallel with hot air (gas inlet temperature: 350 ± 10°C, gas outlet temperature: 140 ± 5°C, throughput: 4.7 kg aqueous mixture M / h and hot air stream with a flow rate of 8.5 m³ (STP) / h) using a Type F01A centrifugal atomizer and a Type SL24-50 atomizer wheel in a Mobile Minor™ 2000 (MM-I) atomizer tower at Niro A / S, Gladsaxevej 305, 2860 Søborg, Denmark. Constant stirring of the proportion of aqueous mixture M that had not yet been spray-dried was continued at 60°C. The speed setting of the atomizer wheel was 25,000 rpm. The generated spray powder was intermediately stored in an airtight container (capacity 200 L, 25°C, atmospheric pressure) until further processing (for 10 calendar days; shorter or longer intermediate storage (up to 30 calendar days) had no effect on the resulting product). The loss on ignition of the obtained spray powder (calcined at 600°C (powder temperature) under stagnant air in excess for 3 hours) was 32% by weight of its initial weight.
[0267] e) Preparation of an annular molded unsupported catalyst precursor body
[0268] 3 kg of spray powder containing 3.5 wt% graphite (Type 3160, Asbury Graphite Mills Inc., New Jersey 08802) based on the weight of the spray powder and 5 wt% glass fiber based on the weight of the spray powder (Glass fiber E-Glass Type F2F 160, Profill GmbH, Heidelberg, Kichheimerstr. 1, D-69214 Eppelheim, Nominal fiber size: 10 μm diameter, 200 μm length, BET surface area 0.4 m² 2 / g) and a mixer equipped with a chopper (mixer type L5 / 10, Gebrüder Lödige Maschinenbau GmbH, Elsener Straße 7-9, 33102 Paderborn, Germany) were mixed for 10 minutes, and the chopper blades were used intermittently for a total of 1 minute.
[0269] Subsequently, the powder mixture produced as described was compressed (tablet-pressed) under a dry air atmosphere using a Kilian E150+ rotary press (containing 21 EURO D dies) to produce an annular molded precursor body having a shape of E x H x I = 5 mm x 5 mm x 2 mm with non-curved (i.e., flat) end faces and a mass (MV) of 160 mg (body density 1.94 g / mL). The applied compressive force (P v The power was 1.6 kN. The rotor speed was 15-20 rpm.
[0270] f) Thermal pretreatment and calcination of the cyclic molded unsupported catalyst precursor body prepared in e)
[0271] 1000 g of the manufactured molded unsupported catalyst precursor body was applied in an air circulation shaft oven (Nabertherm GmbH, D-28865 Lilienthal; oven model S60 / 65A) through which previously dried air (with an entry temperature of 140°C) passed at 4500 L (STP) / h, evenly distributed across four parallel mesh grids each having a square bottom area of 150 mm x 150 mm (layer height: 15 mm) (the circulation oven was located in an environment of 25°C). Subsequently, while maintaining airflow (including its entry temperature), the temperature inside the air circulation shaft oven was varied as follows (temperature values represent the temperature within the applied bulk material for each; this was determined by four thermocouples, each located in the geometric midpoint of the four mesh grids at the center of the bulk material applied to each mesh grid; one thermocouple provided the actual value for temperature control of the air circulation shaft oven; the other thermocouples confirmed that the temperature was identical within ± 0.1°C intervals). The temperature increase was essentially linear over time. Heating was performed from 25°C to 130°C within 72 minutes. This temperature was maintained for 72 minutes, after which it was increased to 190°C within 36 minutes. The temperature was maintained at 190°C for 144 minutes, after which it was increased to 220°C within 36 minutes. After 220°C was maintained for 72 minutes, the temperature rose to 380°C within 93 minutes. The temperature was maintained at 380°C for 187 minutes, then increased to 430°C within 93 minutes. The temperature was maintained at 430°C for 187 minutes, then increased to a final calcination temperature of 500°C within 93 minutes. This was maintained for 467 minutes. Subsequently, cooling to 25°C was achieved within 12 hours. For this purpose, both the heating of the air circulation shaft oven and the preheating of the air stream were turned off (however, the air stream itself at 4500 L (STP) / h was maintained; the inlet temperature of the air stream was then 25°C).Until used for catalytic action of heterogeneous catalytic partial oxidation (e.g., propene to acrolein), the obtained cyclic molded unsupported catalyst body (K1) was stored in a sealed container at a temperature of 25°C and atmospheric pressure.
[0272] Active multimetal oxide is Mo 12 Bi 0.6 Fe3Co 4.9 Ni 2.6 K 0.12 O x Preparation of a molded unsupported catalyst body (K2) having the stoichiometry of
[0273] The preparation of K2 was similar to the preparation of K1. The amount of glass fiber was controlled to 3% by weight based on the weight of the spray powder.
[0274] Active multimetal oxide is Mo 12 Bi 0.6 Fe3Co 4.9 Ni 2.6 K 0.12 O x Preparation of a molded unsupported catalyst body (K3) having the stoichiometry of
[0275] The manufacturing of K3 was similar to that of K1. Glass fiber was not used.
[0276] Active multimetal oxide is Mo 12 Bi 0.6 Fe3Co 4.9 Ni 2.6 K 0.12 O x Preparation of a molded unsupported catalyst body (K4) having the stoichiometry of
[0277] The preparation of K4 was similar to that of K1. Glass fibers were not used. The powder mixture was compressed (tablet-pressed) to form a ring-shaped molded precursor body with a mass (MV) of 185 mg (body density 2.24 g / mL).
[0278] Active multimetal oxide is Mo 12 Bi 0.6 Fe 2.4 Co 6.1 Ni1.6 K 0.04 O x Preparation of a molded unsupported catalyst body (K5) having the stoichiometry of
[0279] The preparation of K5 was similar to the preparation of K2. The amounts of potassium hydroxide solution, cobalt(II) nitrate solution in nitric acid, iron(III) nitrate citric acid melt, bismuth nitrate solution in nitric acid and nickel nitrate solution in nitric acid were adjusted accordingly to achieve the elemental composition.
[0280] Active multimetal oxide is Mo 12 Bi 0.6 Fe 2.4 Co 6.1 Ni 1.6 K 0.04 O x Preparation of a molded unsupported catalyst body (K6) having the stoichiometry of
[0281] The manufacturing of K6 was similar to that of K5. Glass fiber was not used.
[0282] Active multimetal oxide is Mo 12 Bi 0.6 Fe 2.4 Co 6.1 Ni 1.6 K 0.04 O x Preparation of a molded unsupported catalyst body (K7) having the stoichiometry of
[0283] The preparation of K7 was similar to that of K5. No glass fibers were used. The powder mixture was compressed (tablet-pressed) to form a ring-shaped molded precursor body with a mass (MV) of 190 mg (body density 2.30 g / mL).
[0284] Active multimetal oxide is Mo 12 Bi 0.6 Fe 2.4 Co 7.7 K 0.08 O x Preparation of a molded unsupported catalyst body (K8) having the stoichiometry of
[0285] The preparation of K8 was similar to the preparation of K2. The amounts of potassium hydroxide solution, cobalt(II) nitrate solution in nitric acid, iron(III) nitrate citric acid melt, bismuth nitrate solution in nitric acid, and nickel nitrate solution in nitric acid were adjusted accordingly to achieve the elemental composition. The final calcination temperature was adjusted to 480°C.
[0286] Active multimetal oxide is Mo 12 Bi 0.6 Fe 2.4 Co 7.7 K 0.08 O x Preparation of a molded unsupported catalyst body (K9) having the stoichiometry of
[0287] The preparation of K9 was similar to that of K8. The amount of glass fiber was controlled to 4 wt% based on the weight of the spray powder. The powder mixture was compressed (tablet-pressed) to form a ring-shaped molded precursor body having a mass (MV) of 150 mg (body density 1.92 g / mL).
[0288] Active multimetal oxide is Mo 12 Bi 0.6 Fe 2.4 Co 7.7 K 0.08 O x Preparation of a molded unsupported catalyst body (K10) having the stoichiometry of
[0289] The manufacturing of K10 was similar to that of K8. Glass fiber was not used.
[0290] Active multimetal oxide is Mo 12 Bi 0.6 Fe3Co 7.5 K 0.14 O x Preparation of a molded unsupported catalyst body (K11) having the stoichiometry of
[0291] The preparation of K11 was similar to the preparation of K8. The amounts of potassium hydroxide solution, cobalt(II) nitrate solution in nitric acid, iron(III) nitrate citric acid melt, and bismuth nitrate solution in nitric acid were adjusted accordingly to achieve the elemental composition.
[0292] Active multimetal oxide is Mo 12 Bi 0.6 Fe3Co 7.5 K 0.14 O x Preparation of a molded unsupported catalyst body (K12) having the stoichiometry of
[0293] The preparation of K12 was similar to that of K11. The amount of glass fiber was controlled to 4 wt% based on the weight of the spray powder. The powder mixture was compressed (tablet-pressed) to form a ring-shaped molded precursor body having a mass (MV) of 150 mg (body density 1.82 g / mL).
[0294] Active multimetal oxide is Mo 12 Bi 0.6 Fe3Co 7.5 K 0.14 O x Preparation of a molded unsupported catalyst body (K13) having the stoichiometry of
[0295] The manufacturing of K13 was similar to that of K11. Glass fiber was not used.
[0296] To determine mechanical stability, lateral fracture strength (SDF) was determined by Sotax ST-50 (SOTAX AG, Aesch, Switzerland) using a test speed of 0.1 mm / s. The average of 20 measurements is reported.
[0297] Various manufacturing parameters and characteristics of the molded unsupported catalyst bodies (K1 to K13) are summarized in Table 1 below.
[0298]
[0299] Catalyst test for the selective oxidation of propene to acrolein and acrylic acid
[0300] Test Method 1:
[0301] The reaction tube (V2A steel, outer diameter 21 mm, wall thickness 3 mm, inner diameter 15 mm, length 120 cm) was filled from top to bottom according to the flow direction of the subsequent reaction gas mixture as follows:
[0302] Section 1: Length 10 cm
[0303] Steatit balls having a diameter of 1.5 to 2.0 mm as an upstream bed (Steat C220 of CeramTec);
[0304] Section 2: Length 71 cm
[0305] A homogenized mixture of 10 g of an annular molded unsupported catalyst body and 135 g of steatite rings having a shape of 5 mm x 5 mm x 2 mm (outer diameter x length x inner diameter);
[0306] Section 3: Length 10 cm
[0307] Steatit balls having a diameter of 1.5 to 2.0 mm as a downstream bed (Steait C220 of CeramTec).
[0308] The temperature of the reaction tubes was controlled by the salt melts sparged with molecular nitrogen for each (53 wt% potassium nitrate, 40 wt% sodium nitrite, and 7 wt% sodium nitrate). The salt bath (salt melt) was contained in a cylindrical shell with an inner diameter of 11 cm. The cylindrical shell had the same length as the reaction tubes. The latter was guided from top to bottom within the cylindrical shell so that two axes of symmetry coincided. At a temperature of 25°C, the nitrogen flow rate bubbling into the salt bath from the bottom was 40 L (STP) / h (standard conditions = 1.01 bar, 0°C). The heat loss from the salt bath to the ambient environment was greater than the reaction heat released into the salt bath by the tubular reactor during partial oxidation. Therefore, the salt bath was heated by electric heating to its temperature T SB It was maintained at (°C). In this way, the outer wall of the reaction tube was always maintained at the appropriate temperature T SB It was guaranteed to be at (°C).
[0309] T SB It was set to a temperature of 380℃.
[0310] A reaction gas injection mixture having the following composition was continuously filled into the reaction tube:
[0311] 5 volume% propene (polymer grade purity),
[0312] 9.5 volume% of molecular oxygen, and
[0313] 85.5 volume% molecular nitrogen.
[0314] At a temperature of 150°C, the flow rate of the reaction gas input mixture stream supplied to the reaction tube was a constant 70 L (STP) / h. In all cases, the pressure at the inlet to the reaction tube was 1.6 bar absolute pressure (there was a control valve at the outlet of the reaction tube for the purpose of adjusting the inlet pressure).
[0315] The composition of the reaction gas mixture was determined through "online" analysis by gas chromatography at both the inlet and outlet of the reaction tube.
[0316] Propene conversion rate based on a single pass of a reaction gas mixture through a reaction tube (C P (mol%) is the morphophene content C of the reaction gas mixture at the reaction tube inlet. Pin and morphophene content C of the reaction gas mixture at the reaction tube outlet Pout It was determined as follows from:
[0317] C P (mol%) = 100 x (C Pin - C Pout ) / C Pin .
[0318] Molar acrolein content of the reaction gas mixture at the reaction tube outlet (C Aout ), molar acrylic acid content of the reaction gas mixture at the reaction tube outlet (C Sout ) and C Pin and C Pout Selectivity of acrolein formation based on the single passage of a reaction gas mixture through a reaction tube using (S A (mol%)) and selectivity of acrylic acid formation (S S (mol%) was determined as follows:
[0319] S A (mol%) = 100 x (C Aout / (C Pin - C Pout ));
[0320] S S (mol%) = 100 x (C Sout / (C Pin - C Pout )).
[0321] Selectivity S for overall target product formation PV (mol%) is S A (mol%) + S SIt is calculated as the total sum of (mol%).
[0322] The catalytic activity (propene conversion rate, selectivity, yield) measured over 7 consecutive days of testing is shown in Table 2.
[0323] Test Method 2:
[0324] The reactor test plant used in Test Method 1 was used.
[0325] Section 1: Length 10 cm
[0326] Steatit balls having a diameter of 1.5 to 2.0 mm as an upstream bed (Steat C220 of CeramTec);
[0327] Section 2: Length 40-47 cm
[0328] 50 g of pure cyclic molded unsupported catalyst body;
[0329] Section 3: Length 70 cm
[0330] A steatite ring with a shape of 5 mm x 5 mm x 2 mm (outer diameter x length x inner diameter).
[0331] The flow rate of the supplied reaction gas input mixture stream was 100 L (STP) / h. In all cases, the pressure at the inlet of the reaction tube was 1.2 bar absolute pressure (a control valve was installed at the reaction tube outlet for the purpose of adjusting the inlet pressure).
[0332] The reaction tube was continuously filled with a reaction gas injection mixture having the following composition:
[0333] Propene (polymer grade purity) 5 volume%,
[0334] Molecular oxygen 9.5 volume%, and
[0335] 85.5 volume% molecular nitrogen.
[0336] To achieve a 95% propene conversion rate, T SB He changed it accordingly.
[0337] In detail,
[0338] At the start of all partial oxidation tests using fresh fixed bed filler, T SB The temperature was set to 325℃. T SB = Each current propene conversion rate C based on a single pass of the reaction gas mixture through the reaction tube, based on the composition of the product gas mixture generated in each case and the gas chromatographic analysis of the reaction gas input mixture introduced into the reaction tube, for the first time after an operating time of 2 hours at 325°C and until a total operating time of 72 hours is reached thereafter. P and respective generated selectivity S for the formation of the target product PV Determine every 2 hours, and then proceed based on the existing value in each case, the propene conversion rate C based on the single pass of the reaction gas mixture through the reaction tube P This T SB At each newly set value of (T SB (Immediately after resetting) In each case, T becomes 95 mol% SB The value of was increased or decreased. Then T SB The newly set value of remained unchanged for a 2-hour operation period in each case. Propene conversion rate C of 95 mol% P T required in each case for (based on the single pass of the reaction gas mixture through the reaction tube) SB The arithmetic mean of the last 12 values of (°C) (i.e., over a total operating time interval of 48 to 72 hours) is the value T SBend It is (°C). This indicates the activity of each catalyst. Target product S PV The arithmetic mean of the last 12 values determined for (based on a single pass of the reaction gas mixture through the reaction tube) (i.e., over a total operating time interval of 48 to 72 hours) is value S PVend This represents the selectivity of the target product formation for each catalyst.
[0339] Catalytic activity (T SB , propene conversion rate, selectivity) are summarized in Table 3.
[0340] [Table 2]
[0341] Catalytic activity according to Test Method 1.
[0342]
[0343] The molded unsupported catalyst body according to the present invention exhibits a high yield with high mechanical stability at the same time.
[0344] [Table 3]
[0345] Catalytic activity according to Test Method 2
[0346]
[0347] The molded unsupported catalyst body according to the present invention exhibits a high yield with high mechanical stability at the same time.
Claims
Claim 1 A shaped unsupported catalyst body for producing unsaturated aldehydes and unsaturated carboxylic acids, wherein the shaped unsupported catalyst body comprises at least molybdenum, bismuth, iron, and cobalt elements, wherein the shaped unsupported catalyst body comprises inorganic fibers having an average fiber length of 10 μm to 1 mm and an average fiber diameter of 1 μm to 30 μm, and wherein the shaped unsupported catalyst body has a total pore volume of 0.37 to 0.65 mL / g determined by mercury porosity measurement. Claim 2 A molded unsupported catalyst body according to claim 1, wherein the molded unsupported catalyst body has a total pore volume of 0.39 to 0.60 mL / g. Claim 3 A molded unsupported catalyst body according to claim 1 or 2, wherein the inorganic fiber is a glass fiber, an aluminum oxide fiber, a silica fiber, or a carbon fiber. Claim 4 A molded unsupported catalyst body according to any one of claims 1 to 3, wherein the inorganic fiber has an average fiber length of 50 μm to 500 μm and an average fiber diameter of 5 μm to 15 μm. Claim 5 In any one of claims 1 to 4, the composition of the molded unsupported catalyst body is a molded unsupported catalyst body corresponding to the following general formula (I):Mo 12 Bi a Fe b Co c Ni d X e Y f Z g O n (I) In the above formula, X = K, Cs and / or Rb, Y = Ca, Sr, Ba, Li, Na, Cr, W, Mn, Cu, Zn, Ga, P, B, As, Sn, Sb, Te, Nb, Ta, Pb, Ce and / or La, Z = Si, Al, Ti, Zr and / or Mg, a = 0.2 to 2, b = 1 to 4, c = 3 to 9, d = 0 to 4, c + d = 4 to 9.5, e = 0.01 to 0.5, f = 0 to 10, g = 0 to 10, n is a number determined by the valence and frequency of non-oxygen elements in general formula (I). Claim 6 A molded unsupported catalyst body according to claim 5, wherein in general formula (I), X = K, a = 0.4 to 0.8, b = 2.2 to 3.2, c = 4.7 to 7.9, d = 0 to 2.8, c + d = 7.3 to 8.0, e = 0.02 to 0.16, f = 0 and g = 0. Claim 7 A molded unsupported catalyst body comprising 0.1% to 15% by weight of inorganic fibers based on the weight of the molded unsupported catalyst body, in any one of claims 1 to 6. Claim 8 A molded unsupported catalyst body according to any one of claims 1 to 7, wherein the pore volume of the molded unsupported catalyst body in the range of 0.1 to 1 μm is 85% to 99% of the total pore volume, and the pore volume in the range of 0.1 to 1 μm is determined by the mercury porosity measurement method. Claim 9 A molded non-supported catalyst body according to any one of claims 1 to 8, wherein the molded non-supported catalyst body is a tableted molded non-supported catalyst body. Claim 10 In claim 9, the compressed molded unsupported catalyst body has a density of 1.20 to 1.45 g / mL, wherein the density of the molded unsupported catalyst body is the ratio of mass to geometric volume. Claim 11 A method for preparing a molded unsupported catalyst body for producing unsaturated aldehydes and unsaturated carboxylic acids, wherein the molded unsupported catalyst body comprises at least molybdenum, bismuth, iron, and cobalt elements, and the method comprises: a) producing an aqueous solution or aqueous suspension from at least one source for each of the elemental components molybdenum, bismuth, iron, and cobalt, and optionally at least one source for the elemental component nickel; b) drying the aqueous solution or aqueous suspension obtained from a) and optionally performing grinding to produce powder P; c) mixing the powder P obtained from b) with inorganic fibers to produce a powder mixture PM; d) compressing the powder mixture PM obtained from c) after optionally adding one or more auxiliary agents, uniform mixing, and optionally pre-compressing, to provide a molded precursor body having a cylindrical structure; and e) applying the molded precursor body obtained from d) to heat treatment to produce a molded unsupported catalyst A method comprising the step of forming a body, wherein the pressure in the compression in d) is selected such that the density of the formed precursor body is 1.65 to 2.20 g / mL, wherein the density of the formed precursor body is the ratio of mass to geometric volume, and the weight loss in the heat treatment in e) is 15% to 50% by weight. Claim 12 A method according to claim 11, wherein the pressure in compression in d) is selected such that the density of the molded precursor body is 1.75 to 2.10 g / mL and the weight loss in heat treatment in e) is 25% to 40% by weight. Claim 13 In paragraph 11, a method in which the mixing performed in c) is a dry mixing. Claim 14 A method in which, in any one of paragraphs 11 to 13, the compression performed in d) is a tablet. Claim 15 A method for producing unsaturated aldehydes and unsaturated carboxylic acids, comprising guiding alkenes and / or alcohols with molecular oxygen through a fixed catalyst bed comprising a bed of a molded unsupported catalyst body according to any one of claims 1 to 10. Claim 16 A fixed-bed reactor comprising a bed of a molded unsupported catalyst body according to any one of claims 1 to 10. Claim 17 Use of a molded unsupported catalyst body according to any one of claims 1 to 10 in the gas-phase oxidation of alkenes and / or alcohols.
